Artificial graphite material for negative electrode of lithium ion secondary battery and method for producing the same
Patent Information
- Application Number
- CN202180042865.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-06-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-06-18
AI Technical Summary
因此,锂离子二次电池的容量劣化
[0033]本发明提供即使在-10℃的低温下反复充放电而放电容量也不易劣化的锂离子二次电池负极用人造石墨材料及其制造方法、以及锂离子二次电池用负极、及锂离子二次电池。
Smart Images

Figure BDA0003998239150000371 
Figure BDA0003998239150000381 
Figure BDA0003998239150000491
Abstract
Description
Technical Field
[0001] This invention relates to artificial graphite materials for the negative electrode of lithium-ion secondary batteries and their manufacturing methods.
[0002] This application claims priority based on Japanese Patent Application No. 2020-105303, filed on June 18, 2020, the contents of which are incorporated herein by reference. Background Technology
[0003] Lithium-ion secondary batteries are used in various industries, including automotive applications and power storage for public infrastructure systems.
[0004] As the negative electrode material for lithium-ion secondary batteries, graphite, such as artificial graphite materials, is used (see, for example, Patent Document 1).
[0005] Batteries suitable for automotive applications are used over a wide temperature range, from below 0°C to above 60°C. However, for lithium-ion secondary batteries using graphite as the negative electrode material, charging at temperatures below 0°C presents the problem of lithium metal deposition on the negative electrode. This deposition reduces the number of lithium ions that can move between the positive and negative electrodes, leading to capacity degradation in the lithium-ion secondary battery.
[0006] The progress of capacity degradation due to the difference in charge-discharge efficiency between the positive and negative electrodes was reported when lithium metal was not deposited on the negative electrode (see, for example, non-patent literature 1-3).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent No. 5415684
[0010] Non-patent literature
[0011] Non-Patent Document 1: Summary of the 51st Battery Symposium 3G15 (November 8, 2008, Japan)
[0012] Non-patent document 2: Journal of the Fuel Association, Vol. 58, No. 642 (1979), pp. 257-263
[0013] Non-Patent Literature 3: Carbon, 1981 (No. 105), pp. 73-81 Summary of the Invention
[0014] The problem that the invention aims to solve
[0015] For lithium-ion batteries using graphite as the negative electrode material, suppressing capacity degradation caused by charging and discharging at temperatures below 0°C has become a challenge. This is especially true for industrial lithium-ion batteries used in automotive applications and power storage systems for public infrastructure, which require operation over a wide temperature range. Therefore, there is a further demand for lithium-ion rechargeable batteries and their negative electrode graphite materials that can suppress capacity degradation even during charging and discharging at low temperatures.
[0016] The present invention was made in view of the above circumstances, and provides an artificial graphite material for a negative electrode of a lithium-ion secondary battery that does not easily degrade in discharge capacity even when repeatedly charged and discharged at a low temperature of -10°C, a method for manufacturing the same, a negative electrode for a lithium-ion secondary battery, and a lithium-ion secondary battery.
[0017] Methods for solving problems
[0018] The present invention includes the following solutions.
[0019] [1] A method for manufacturing an artificial graphite material for the negative electrode of a lithium-ion secondary battery, comprising at least the following steps:
[0020] The process of producing a raw material carbon composition by coking a raw material oil composition through a delayed coking process;
[0021] The process of heat-treating the above-mentioned raw material carbon composition to obtain a heat-treated raw material carbon composition;
[0022] The process of pulverizing the above-mentioned heat-treated raw material carbon composition to obtain raw material carbon powder;
[0023] The process of graphitizing the above-mentioned raw carbon powder to obtain graphite powder; and
[0024] The process of pulverizing the above-mentioned graphite powder
[0025] The volatile content of the above-mentioned raw material carbon powder is less than 3.71%, and the true density of the above-mentioned raw material carbon powder is greater than 1.22 g / cm³. 3 And below 1.73 g / cm 3 .
[0026] [2] In the method for manufacturing artificial graphite material for lithium-ion secondary battery negative electrode as described in [1] above, the heat treatment temperature of the process for obtaining the above-mentioned heat treatment raw material carbon composition is 500°C or higher and 700°C or lower.
[0027] [3] The method for manufacturing artificial graphite material for lithium-ion secondary battery negative electrode as described in [1] or [2] above, wherein the content of n-chain alkanes in the above raw material oil composition is 5 to 20% by mass, and the aromatic index fa obtained by the Knight method is 0.3 to 0.65.
[0028] [4] A negative electrode for a lithium-ion secondary battery, comprising artificial graphite material obtained by any one of the manufacturing methods described in [1] to [3] above.
[0029] [5] A lithium-ion secondary battery having the negative electrode described in [4] above.
[0030] [6] An artificial graphite material for the negative electrode of a lithium-ion secondary battery, characterized in that the nitrogen adsorption specific surface area S(BET) is 2.5–6.2 m². 2 / g,
[0031] Using the X-band electron spin resonance method, an absorption spectrum originating from carbon radicals appearing near g = 2.0 was obtained. The ratio of spin density I(4.8K) (spins / g) to S(BET), calculated from the signal intensity at 4.8K, is I(4.8K) / S(BET) = 5.2 × 10⁻⁶. 17 ~6.8×10 17 spins / m 2 .
[0032] Invention Effects
[0033] This invention provides an artificial graphite material for a lithium-ion secondary battery anode that does not easily degrade in discharge capacity even after repeated charging and discharging at a low temperature of -10°C, a method for manufacturing the same, an anode for a lithium-ion secondary battery, and a lithium-ion secondary battery. Attached Figure Description
[0034] Figure 1 This is a schematic cross-sectional view showing an example of a lithium-ion secondary battery according to this embodiment. Detailed Implementation
[0035] The following provides a detailed description of the artificial graphite material for the negative electrode of a lithium-ion secondary battery, its manufacturing method, the negative electrode for a lithium-ion secondary battery, and consequently, the lithium-ion secondary battery. It should be noted that the present invention is not limited to the embodiments shown below.
[0036] <<Artificial Graphite Materials for Negative Electrodes of Lithium-ion Secondary Batteries>>
[0037] The artificial graphite material of this embodiment satisfies all of the conditions (1) to (2) below. Furthermore, the artificial graphite material of this embodiment preferably satisfies all of the conditions (1) to (3) below.
[0038] (1) The nitrogen adsorption specific surface area S(BET) is 2.5–6.2 m². 2 / g.
[0039] (2) Using the X-band electron spin resonance method, an absorption spectrum originating from carbon free radicals appearing near g = 2.0 was obtained. The ratio of spin density I(4.8K) (spins / g) to S(BET), calculated from the signal intensity at 4.8K, is 5.2 × 10⁻⁶. 17 ~6.8×10 17 spins / m 2 .
[0040] (3) The size L(112) of the microcrystal, calculated from the (112) diffraction line determined by X-ray wide-angle diffraction, is 4 to 30 nm.
[0041] The nitrogen adsorption specific surface area S(BET) in condition (1) above is the nitrogen adsorption specific surface area (m²) measured and calculated according to JIS Z 8830 (2013) "Method for determination of specific surface area of powder (solid) by gas adsorption". 2 / g). The specific surface area determined and calculated by this method will be referred to as "specific surface area" below.
[0042] In condition (2) above, I(4.8K) is the spin density (spins / g) calculated from the signal intensity of the absorption spectrum originating from carbon radicals appearing near g=2.0, when the ESR measurement is performed under the following conditions: the graphite material is placed in the sample tube and vacuumed, and then He gas is sealed in the sample tube. The conditions are X-band microwave (9.60 GHz), intensity 1 mW, central magnetic field 3412 G, magnetic field modulation 100 kHz, and measurement temperature 4.8 K. ESR spectra are usually obtained by first differential spectroscopy. If first integration is performed, it becomes the absorption spectrum. If second integration is performed, the signal intensity can be obtained. The spin density calculated from the signal intensity becomes an index representing the density of unpaired electrons in the material. Therefore, the ratio I(4.8K) / S(BET) in condition (2) above is an index representing the density of unpaired electrons per unit surface area, which will be abbreviated as I(4.8K) / S(BET) below.
[0043] In condition (3) above, the crystallite size L(112) calculated from the (112) diffraction line determined by wide-angle X-ray diffraction is L(112) determined and calculated according to JIS R 7651 (2007) "Method for determination of lattice constant and crystallite size of artificial graphite materials". Sometimes L(112) determined and calculated by this method is abbreviated as L(112) below.
[0044] The inventors conducted repeated and in-depth research on the size of microcrystals, nitrogen adsorption specific surface area, and I(4.8K) / S(BET) of artificial graphite materials. They discovered that by fabricating a lithium-ion secondary battery with a negative electrode containing artificial graphite materials that satisfy all of the above conditions (1) to (2), preferably all of the above conditions (1) to (3), it is possible to suppress the degradation of discharge capacity during repeated charging and discharging at temperatures below -10°C, thereby completing the present invention.
[0045] It possesses the following conditions: (1) "The nitrogen adsorption specific surface area is 2.5–6.2 m²". 2 Lithium-ion secondary batteries with a negative electrode made of artificial graphite material ( / g) do not easily suffer from capacity degradation even after repeated charge-discharge cycles at temperatures below -10°C. If the nitrogen adsorption specific surface area is 2.5m²... 2 With a nitrogen adsorption specific surface area of 6.2 m² / g or higher, the precipitation suppression effect of lithium metal in the negative electrode due to the large nitrogen adsorption specific surface area can be fully obtained. Furthermore, the nitrogen adsorption specific surface area is 6.2 m² / g. 2 Artificial graphite materials with a specific surface area of less than 10 g will not hinder the insertion reaction of lithium ions into graphite crystals during charging at low temperatures below -10°C due to steric hindrance caused by the non-organic carbon on the particle surface generated by the crushing of graphite powder during manufacturing.
[0046] Here, unorganized carbon refers to the texture of carbon atoms not incorporated into the hexagonal carbon network plane. Its chemical structure is not necessarily defined, but it is considered to be a complex texture formed by dangling bonds created by the mechanical energy that breaks the chemical bonds constituting the hexagonal network plane (see, for example, "Carbon Terminology Dictionary," pp. 354-355 (AGNE Shofu, October 5, 2000)). Therefore, unorganized carbon functions as a steric hindrance for the reversible insertion reaction into graphite during charging and discharging, making it easier for lithium metal to deposit during charging. As mentioned above, unorganized carbon is produced by pulverizing graphite powder during manufacturing; therefore, when pulverized to a size of 6.2 μm... 2 When the carbon content is below a certain value, the contribution of non-organic carbon as steric hindrance is small.
[0047] In contrast, during manufacturing, the graphite powder is pulverized to a size exceeding 6.2 m² based on the nitrogen adsorption specific surface area. 2 Artificial graphite with a particle size of / g introduces a large amount of non-organic carbon onto its particle surface, increasing the steric hindrance contribution to the reversible lithium-ion intercalation reaction. In particular, if charging is performed at low temperatures below -10°C where the electrolyte viscosity decreases, lithium ions become more readily deposited, making this method undesirable.
[0048] Having the above conditions (2), "using the X-band electron spin resonance method, it has an absorption spectrum originating from carbon free radicals appearing near g = 2.0, and the ratio of the spin density I(4.8K) calculated from the absorption intensity at temperature 4.8K to the above S(BET) is I(4.8K) / S(BET) = 5.2 × 10⁻⁶". 17 ~6.8×10 17 The lithium-ion secondary battery with an anode made of artificial graphite material does not easily degrade in discharge capacity even after repeated charge-discharge cycles at temperatures below -10°C. Here, I(4.8K) represents the spin density (spins / g) of unpaired electrons (localized electrons) introduced into the non-organic carbon through the pulverization of graphite powder during manufacturing. Furthermore, I(4.8K) / S(BET) mainly represents the amount of non-organic carbon introduced per unit area (spins / m²) onto the particle surface. 2 The reasons for this will be explained in detail below.
[0049] ESR measurement is a spectroscopic analysis that observes the energy level transitions produced when unpaired electrons are placed in a magnetic field. When a magnetic field is applied to a substance containing unpaired electrons, the energy levels are split into two parts by the Zeeman effect. Measurements are performed by scanning the magnetic field under microwave irradiation; however, as the applied magnetic field increases, the energy splitting interval, ΔE, increases. Resonant absorption is observed when ΔE becomes equal to the energy of the irradiated microwave. By detecting the amount of energy absorbed at this point, the ESR spectrum can be obtained. The ESR spectrum is usually obtained from a first-order differential spectrum; a first-order integration yields the absorption spectrum, and a second-order integration yields the signal intensity. The magnitude of this signal intensity becomes an indicator of the density of unpaired electrons in the substance. In graphite crystals, there are two types of unpaired electrons: localized electrons and conduction electrons. Therefore, in ESR measurements of graphite, the sum of the microwave resonant absorptions caused by these two types of unpaired electrons is observed as the ESR spectrum. The signal intensity obtained by double integration of the ESR spectrum becomes an index representing the magnitude of the unpaired electron density, which is the sum of the conduction electron density and the localized electron density. Here, the conduction electrons in graphite are unpaired π electrons that spontaneously manifest themselves in relation to the number of rings forming the hexagonal lattice plane and their bonding form, and can move freely within the hexagonal lattice plane (see, for example, Carbon 1966 No. 47 30-34, 1967 No. 50 20-25).
[0050] On the other hand, localized electrons are stationary electrons existing on the edge surfaces of a hexagonal planar laminate. Furthermore, the signal intensity of resonant absorption generated by conduction electrons is not temperature-dependent; in contrast, the signal intensity of resonant absorption generated by localized electrons increases inversely with the measurement temperature T. For example, in ESR measurements of carbon materials within the temperature range of 4.2 K ≤ T ≤ 300 K, when measurements were performed by slowly decreasing the measurement temperature from 300 K, microwave absorption generated by localized electrons began to be observed near 50 K. In the low-temperature region below 50 K, the signal intensity generated by localized electrons increased dramatically inversely with the measurement temperature T (see, for example, Carbon 1996 No. 175 249-256). Therefore, the spin density I (4.8 K) calculated from the absorption intensity at 4.8 K can be considered an indicator of the density of localized electrons. Furthermore, the localized electrons introduced through the crushing of graphite powder during manufacturing are introduced into the fracture surface, i.e. the particle surface. Therefore, the ratio of I(4.8K) to nitrogen adsorption specific surface area S(BET) I(4.8K) / S(BET) is regarded as an indicator of the amount of localized electron spin per unit area of the particle surface.
[0051] The artificial graphite material of this embodiment satisfies the above condition (2). That is, by using the X-band electron spin resonance method, it has an absorption spectrum originating from carbon free radicals appearing near g = 2.0, and the ratio of the spin density signal intensity I(4.8K) calculated from the absorption intensity at 4.8K to the above-mentioned S(BET), I(4.8K) / S(BET), satisfies 5.2 × 10⁻⁶. 17 ~6.8×10 17 In particular, the highly crystalline graphite powder with a crystallite size L(112) of 4–30 nm under the above condition (3) was pulverized to a nitrogen adsorption specific surface area of 2.5–6.2 m² based on the volumetric surface area under the above condition (1). 2 With a density up to / g, the three-dimensional order of carbon atoms in the fracture surface is greatly reduced, and the localized electron density per unit area, i.e., I(4.8K) / S(BET), increases, typically reaching 7.0×10⁻⁶. 17 (spins / m 2 )above.
[0052] In contrast, the artificial graphite in this embodiment satisfies I(4.8K) / S(BET) of 5.2 × 10⁻⁶. 17 ~6.8×10 17 In other words, the artificial graphite in this embodiment is the localized electron density (spins / m²) introduced onto the particle surface through the pulverization of graphite powder during manufacturing. 2Low carbon content, or in other words, low amount of non-organic carbon introduced into the particle surface of graphite materials. Because there is little non-organic carbon that functions as a steric hindrance for the reversible insertion of lithium ions, lithium metal is not easily deposited even when charging at low temperatures below -10°C, and the degradation of discharge capacity during repeated charge and discharge in this temperature range can be suppressed.
[0053] Although it is also possible to manufacture I(4.8K) / S(BET) below 5.2×10 17 Artificial graphite materials are used, but if lithium-ion secondary batteries using such artificial graphite in the negative electrode are charged at temperatures below -10°C, a significant decrease in discharge capacity (deterioration of charge / discharge capacity) is observed. The reason for this is unclear, but it is believed that due to the low amount of localized electrons on the particle surface—that is, the insufficient amount of non-organic carbon on the particle surface—when charging at temperatures below -10°C, lithium ions are embedded in the graphite crystals, while the electrolyte solvent co-intercalates, resulting in reduction and decomposition between the crystalline layers. For these reasons, the range of I(4.8K) / S(BET) is limited to I(4.8K) / S(BET) of 5.2 × 10⁻⁶. 17 ~6.8×10 17 .
[0054] The artificial graphite material with an L(112) of 4–30 nm in the above condition (3) has highly developed crystal structure. Artificial graphite materials with an L(112) of 4–30 nm have a suitable degree of graphitization as negative electrodes for lithium-ion secondary batteries. The larger the L(112), the larger the reversible capacity. Therefore, the L(112) of artificial graphite materials is preferably 4 nm or more. Artificial graphite materials with an L(112) of less than 4 nm sometimes have insufficiently developed crystal structure. Therefore, lithium-ion secondary batteries with negative electrodes containing artificial graphite materials with an L(112) of less than 4 nm sometimes have small capacity and are not preferred (for example, refer to "Carbon Materials for Negative Electrodes of Lithium-ion Secondary Batteries" pp. 3-4 (Realize Corporation, October 20, 1996)).
[0055] <<Manufacturing Method of Artificial Graphite Material for Negative Electrode of Lithium-ion Secondary Batteries>>
[0056] The artificial graphite material of this embodiment can be manufactured, for example, by the manufacturing method shown below.
[0057] That is, the method for manufacturing the artificial graphite material for the negative electrode of the lithium-ion secondary battery in this embodiment includes at least:
[0058] The process of coking a feedstock oil composition through a delayed coking process to produce a feedstock carbon composition (hereinafter also referred to as "Process A");
[0059] The process of heat-treating the above-mentioned raw material carbon composition to obtain a heat-treated raw material carbon composition (hereinafter also referred to as "Process B");
[0060] The process of pulverizing the above-mentioned heat-treated raw material carbon composition to obtain raw material carbon powder (hereinafter also referred to as "process C");
[0061] The process of graphitizing the above-mentioned raw carbon powder to obtain graphite powder (hereinafter also referred to as "Process D"); and
[0062] The process of pulverizing the above-mentioned graphite powder (hereinafter also referred to as "Process E").
[0063] In the method for manufacturing artificial graphite material for the negative electrode of a lithium-ion secondary battery according to this embodiment, the volatile content of the raw material carbon powder is less than 3.71%, preferably 0.1% or more and 3.6% or less, and the true density of the raw material carbon powder exceeds 1.22 g / cm³. 3 And below 1.73 g / cm 3 The preferred value is 1.26 g / cm³. 3 Above and 1.68 g / cm 3 the following.
[0064] The volatile components of the aforementioned raw material carbon powder were calculated based on the volatile components [mass fraction (%)] of "7.2 Vertical tubular electric furnace method" and "b) coke case" in "7. Quantitative methods for volatile components" of JIS M 8812 (2004), "Coal and coke - Industrial analysis methods". The volatile components calculated by this method will be referred to as "volatile components" below.
[0065] The true density of the aforementioned raw material carbon powder was calculated according to "7.3 True Density Test Method" of "7. Density and Porosity Test Method" in JIS K 2151 (2004), "Coke - Test Methods". [g / cm³] 3 The true density calculated using this method will be referred to as "true density" below.
[0066] The reason why it is presumed that when this artificial graphite material is used as the negative electrode of a lithium-ion secondary battery, the degradation of discharge capacity can be suppressed even at a low temperature of -10°C due to the fact that the fracture initiation point generated by the combination of heat treatment and subsequent pulverization of the raw carbon composition remains even after graphitization. Pulverization is generated starting from this fracture initiation point, resulting in a decrease in the amount of non-organic carbon introduced into the fracture surface.
[0067] The heat treatment of the raw carbon composition reduces volatile components, but creates evaporation paths for these volatile components—i.e., tortuous pores of various sizes—on its surface and throughout its interior. Through the mechanical energy generated by pulverization following this heat treatment, small-diameter pores grow as cavities (cracks), while large-diameter pores, after growth, undergo cleavage (pulverization). These cavities, even after graphitization, remain as lattice defects and act as fracture initiation points during subsequent pulverization. The lattice defects (the aforementioned cavities) remain in the fracture surface created by such pulverization, leading to the breaking of chemical bonds in the fracture regions outside the lattice defects. Because the breaking of chemical bonds does not occur throughout the fracture surface, the amount of non-organic carbon introduced through pulverization is less than that introduced in a pulverized fracture surface where lattice defects are absent, compared to a pulverized fracture surface where lattice defects are absent. The non-organic carbon that functions as a steric hindrance for reversible lithium-ion intercalation is small, so lithium metal is not easily deposited even when charging at low temperatures below -10°C, which can suppress the degradation of discharge capacity during repeated charging and discharging in this temperature range.
[0068] The true density of the feedstock carbon composition produced by coking a feedstock oil composition through a delayed coking process is typically 1.1–1.4 g / cm³. 3 Furthermore, the volatile content is typically 5-15% (Non-Patent Literature 2). As a general change resulting from heat treatment of a raw material carbon composition with such properties, the volatile content decreases and the true density increases. The reason for the decrease in volatile content is that the volatile components contained in the raw material carbon composition are reaction products of the raw material oil composition remaining in a state of incomplete thermal decomposition and condensation reaction during the delayed coking process, and therefore dispersed through subsequent heat treatment. The reason for the increase in true density is that the aforementioned thermal decomposition and condensation reactions are further carried out through heat treatment. If the volatile content of the raw material carbon powder obtained by pulverizing a raw material carbon composition with such properties after heat treatment is reduced to less than 3.71%, preferably to more than 0.1% and less than 3.6%, and the true density of the aforementioned raw material carbon powder is increased to more than 1.22 g / cm³, then the volatile content is reduced to less than 3.71%, preferably to more than 0.1% and less than 3.6%. 3 And below 1.73 g / cm 3 Optimized to 1.26 g / cm 3 Above and 1.68 g / cm 3 Therefore, the aforementioned fracture initiation points of appropriate size are introduced in large quantities, so the resulting artificial graphite material for lithium-ion secondary battery anodes can appropriately suppress the degradation of discharge capacity even under repeated charge and discharge at -10°C.
[0069] When the heat treatment reaction of the raw carbon composition is excessive, for example when the volatile content of the raw carbon powder is less than 0.1% and the true density is greater than 1.68 g / cm³, the reaction is not carried out properly.3 In this case, the growth of the hexagonal network plane formed by carbon atoms is too large, so even if it is subsequently crushed, it is impossible to introduce the aforementioned fracture initiation points of appropriate size. Therefore, if the resulting artificial graphite material is repeatedly charged and discharged at -10°C, its discharge capacity will be greatly degraded.
[0070] Conversely, if the heat treatment of the raw carbon composition is insufficient, and the volatile content of the raw carbon powder is above 3.7% and the true density is 1.22 g / cm³, then... 3 The following process only delays the evaporation of relatively low molecular weight compounds resulting from insufficient thermal decomposition and condensation reactions during the coking process, thus failing to form fracture initiation points of appropriate size. Consequently, the discharge capacity of the resulting artificial graphite material deteriorates significantly when repeatedly charged and discharged at -10°C. Therefore, the volatile content of the heat-treated raw carbon powder is limited to below 3.71%, and the true density is limited to above 1.22 g / cm³. 3 And below 1.73 g / cm 3 .
[0071] The following describes in detail each step of the manufacturing method of the artificial graphite material for the negative electrode of the lithium-ion secondary battery according to this embodiment.
[0072] [Process A]
[0073] Examples of feedstock compositions used in process A include fluidized bed catalytic cracking oil (FCC DO), heavy oil subjected to advanced hydrodesulfurization treatment, vacuum distillation residue (VR), coal liquefaction oil, solvent-extracted coal oil, atmospheric distillation residue, shale oil, tar sand pitch, naphtha tar pitch, coal tar pitch, and ethylene bottom oil. Furthermore, compositions obtained by hydrorefining or other treatments of any of the aforementioned heavy oils can also be used as feedstock compositions.
[0074] As the feedstock composition in step A, heavy oil containing a moderate amount of saturated components and moderate amounts of n-alkanes, and subjected to extensive hydrodesulfurization treatment, is particularly preferred. As the feedstock composition, a single heavy oil can be used, or two or more heavy oils can be mixed. When two or more heavy oils are mixed as the feedstock composition, the blending ratio of each heavy oil can be appropriately adjusted according to the properties of each heavy oil. It should be noted that the properties of each heavy oil vary depending on the type of crude oil, the processing conditions from crude oil to the point where the heavy oil is obtained, etc.
[0075] The feedstock oil composition in step A preferably uses a composition containing components that generate a good monolithic mesophase during coking and components that generate a gas that reduces the size of the monolithic mesophase during the condensation, carbonization, and solidification of the monolithic mesophase.
[0076] As a component that generates a good integral intermediate phase in the feedstock oil composition in step A, heavy oil components with an aromatic index (fa) within a specified range as determined by the Knight method can be listed. In the method for manufacturing artificial graphite material according to this embodiment, as the feedstock oil composition, a composition with an aromatic index (fa) of 0.30 to 0.65 as determined by the Knight method is preferred, a composition with an aromatic index (fa) of 0.35 to 0.60 is more preferred, and a composition with an aromatic index (fa) of 0.40 to 0.55 is even more preferred.
[0077] Here, the aromatic index fa is the aromatic carbon fraction determined using the Knight's method. In the Knight's method, the distribution of carbon is used as a metric. 13 The C-NMR spectrum of aromatic carbons is divided into three components (A1, A2, A3). A1 represents the number of carbons within the aromatic ring (half the number of substituted and unsubstituted aromatic carbons). 13 The peak at approximately 40–60 ppm in C-NMR indicates that A2 represents the unsubstituted remaining half of the aromatic carbon (equivalent to…). 13 The peak at approximately 60–80 ppm in C-NMR is A3, which represents an aliphatic carbon number (equivalent to…). 13 The C-NMR peaks are approximately 130–190 ppm. The aromatic index fa is calculated using A1, A2, and A3 by fa = (A1 + A2) / (A1 + A2 + A3). 13 C-NMR is the most fundamental and best method for quantitatively determining the chemical structural parameters of bitumen, namely fa (see, for example, non-patent literature 3).
[0078] If the aromatic index fa of the feedstock oil composition in step A is 0.3 or higher, the combination of heat treatment of the feedstock carbon composition and subsequent pulverization increases the probability of forming a fracture initiation point of appropriate size, resulting in severable pulverization after graphitization. Furthermore, if the aromatic index fa is 0.65 or lower, the gases generated during coking can confine the overall mesophase to a small size, which is preferable. The boundaries of adjacent mesophases easily form the aforementioned fracture initiation point through subsequent pulverization, thus increasing the probability of severable pulverization after graphitization. Conversely, if the aromatic index fa exceeds 0.65, many mesophases are rapidly generated in the matrix during coking, and the rate of aggregation of mesophases becomes faster than the individual growth rate of the mesophases. As a result, the effect of reducing the overall mesophase size by the gases generated during coking cannot be fully obtained, and it may not be possible to confine it to a small size. Furthermore, if the aromatic index fa is below 0.3, the fracture initiation points generated during the pulverization of the raw carbon composition after heat treatment tend to grow significantly, greatly increasing the probability of achieving pulverization. As a result, the number of fracture initiation points remaining after graphitization is reduced beyond what is necessary, making it difficult to achieve severable pulverization during the post-graphitization pulverization process, which is therefore undesirable.
[0079] Examples of components that contribute to the formation of gases that reduce the overall intermediate phase in the feedstock composition of step A include n-chain alkanes. In the method for manufacturing artificial graphite material according to this embodiment, a composition containing 5 to 20% by mass of n-chain alkanes is preferably used as the feedstock composition, and a composition containing 10 to 15% by mass is more preferably used.
[0080] The n-alkane content of the feedstock oil composition in process A refers to the value determined by gas chromatography equipped with a capillary column. Specifically, after identification using a standard reference for n-alkane, a sample of non-aromatic components separated by elution chromatography is passed through a capillary column for determination. The n-alkane content, based on the total mass of the feedstock oil composition, can be calculated from this determination.
[0081] In process A, the n-chain alkanes contained in the feedstock composition generate gas during coking. This gas plays an important role in limiting the size of the overall mesophase generated during coking to a small size, and further limiting the size of the mesophase itself. In addition, the gas generated during coking also functions to uniaxially orient adjacent mesophases that are limited to a small size, thus creating a fine structure with selective orientation.
[0082] If the n-alkanes content of the feedstock oil composition in step A is 5% by mass or more, the excessive growth of the overall mesophase can be suppressed, making it easier to form appropriately sized carbon hexagonal network planar laminates. Furthermore, if the n-alkanes content of the feedstock oil composition is 20% by mass or less, the amount of gas generated from the n-alkanes will not become excessive. If excessive gas is generated during coking, the fracture initiation points generated by the pulverization after heat treatment of the feedstock carbon composition tend to grow larger, dramatically increasing the probability of achieving pulverization. As a result, the number of fracture initiation points remaining after graphitization is reduced excessively, making it difficult to achieve pulverization, which is therefore undesirable.
[0083] As described above, the feedstock oil composition in step A preferably contains 5 to 20% by mass of n-alkanes, and has an aromatic index (fa) of 0.3 to 0.65 determined by the Knight method. By coking such a feedstock oil composition using a delayed coking process, the boundaries of adjacent mesophases are moderately introduced. Through a combination of heat treatment of the feedstock carbon composition and subsequent pulverization, a fracture initiation point of appropriate size that can remain even in subsequent graphitization is formed. As a result, the probability of producing severable pulverization through graphitization is increased.
[0084] As the feedstock oil composition in process A, it is more preferable that the n-chain alkane content and aromatic index fa are within the above-mentioned ranges, and the density D is 0.91 to 1.02 g / cm³. 3 The composition is particularly preferred to have a viscosity V of 10 to 220 mm. 2 A composition of / s.
[0085] In step A, as a method for coking the feedstock oil composition using a delayed coking process, a known method described in Patent Document 1 can be used, for example. The method of coking the feedstock oil composition using a delayed coking process is very suitable for the mass production of high-quality artificial graphite materials.
[0086] In step A, a delayed coking process is used as a method for coking the feedstock oil composition. Through coking, the feedstock oil composition undergoes thermal decomposition and condensation reactions, and a feedstock carbon composition is obtained by generating a large liquid crystal, known as an intermediate phase, as an intermediate product.
[0087] Conditions for the delayed coking unit, for example, the pressure is preferably 0.1 to 0.8 MPa, more preferably 0.2 to 0.6 MPa.
[0088] Furthermore, the temperature is preferably 400–600°C, and more preferably 490–540°C.
[0089] In the manufacturing method of this embodiment, the size of the carbon hexagonal network plane constituting the mesophase is controlled by the gas generated from the feedstock composition during coking. Therefore, the residence time of the gas generated from the feedstock composition during coking within the system is an important control parameter for determining the size of the carbon hexagonal network plane. The residence time of the gas generated during coking within the system can be adjusted by the pressure during coking.
[0090] Therefore, if the pressure during coking is within the preferred range described above, it becomes easier to limit the rate at which gas generated from the feedstock composition is released out of the system.
[0091] Furthermore, if the temperature during coking is within the preferred range described above, a better mesophase can be grown from the feedstock oil composition adjusted to achieve the effects of the present invention.
[0092] Conversely, if the temperature is too low and the pressure is too high during coking, the amount of gas generated during coking becomes insufficient, and the crystal structure of the raw material carbon composition grows excessively. In this case, it becomes difficult to form pores with openings and irregularities on the particle surface of the heat-treated raw material carbon composition produced by heat treatment in step B described later, which is therefore undesirable.
[0093] Furthermore, when the temperature and pressure are too high and too low during the coking process, the amount of gas generated during coking becomes excessive. Even if heat treatment is carried out in the subsequent graphitization process, the graphite crystal structure is not easy to grow and does not exhibit high capacity. Therefore, artificial graphite material is not preferred as a negative electrode for lithium-ion secondary batteries.
[0094] In the method for manufacturing artificial graphite material according to this embodiment, the raw material carbon composition generated by coking is a composition containing raw coke.
[0095] [Process B]
[0096] In process B, the raw material carbon composition generated by coking is heat-treated to obtain a heat-treated raw material carbon composition.
[0097] As a method for obtaining raw carbon powder by heat treatment of a raw carbon composition, examples include heat treatment in an atmosphere of inert gas such as nitrogen, argon, or helium, with a maximum temperature preferably 450–750°C, more preferably 500–700°C, and even more preferably 550–650°C, and a holding time preferably 0.1–3 hours, more preferably 0.2–2 hours, and even more preferably 0.5–1 hour. Oxygen can also be introduced into the atmosphere at a volume percentage of 0.01–21%. Examples of heating methods include feeding the raw carbon composition into a crucible and using a roller hearth furnace, or directly feeding the raw carbon composition into a rotary kiln.
[0098] The volatile content and true density of the raw carbon powder in step B are related to the heat treatment temperature and time of the raw carbon composition. Generally, the higher the heat treatment temperature or the longer the heat treatment time, the lower the volatile content of the heat-treated raw carbon composition and the resulting raw carbon powder, and the higher the true density. The heat treatment temperature and time of the raw carbon composition must be such that the volatile content of the raw carbon powder is below 3.71% and the true density of the raw carbon powder exceeds 1.22 g / cm³. 3 And below 1.73 g / cm 3 It is set in this way.
[0099] To facilitate the adjustment of the volatile components and true density of the raw carbon powder to these ranges, and to enable the setting of a short heat treatment time to suppress manufacturing costs, the maximum heat treatment temperature of the raw carbon composition is preferably 450°C or higher, more preferably 500°C or higher, and even more preferably 550°C or higher. To facilitate the adjustment of the volatile components and true density of the raw carbon powder to these ranges, and to improve the quality stability of the heat-treated raw carbon composition and raw carbon powder, the maximum heat treatment temperature of the raw carbon composition is preferably 750°C or lower, more preferably 700°C or lower, and even more preferably 650°C or lower.
[0100] If the heat treatment temperature is too low, a longer processing time is required, unnecessarily increasing manufacturing costs, which is therefore not preferable. Furthermore, if the heat treatment temperature is too high, the inhomogeneity of the properties (volatile components and true density) of the heat-treated raw carbon composition and raw carbon powder increases, which is not preferable from the viewpoint of quality stability.
[0101] [Process C]
[0102] In step C, the heat-treated raw carbon composition generated by heat treatment is pulverized to obtain raw carbon powder. As a method for obtaining the raw carbon powder, known methods such as hammer milling can be used, and there are no particular limitations.
[0103] The raw carbon powder can also be graded according to a specified particle size. The average particle size of the raw carbon powder is preferably 5–40 μm. The average particle size of the raw carbon powder is determined using a laser diffraction particle size analyzer. If the average particle size of the raw carbon powder is less than 40 μm, the resulting artificial graphite material, obtained by graphitizing and pulverizing it, has a suitable particle size for use as the negative electrode in lithium-ion secondary batteries. If the average particle size of the raw carbon powder is 5 μm or more, the specific surface area of the artificial graphite material obtained by graphitizing and pulverizing it will not become excessively large, which is preferable. If a graphite material with an excessively large specific surface area is used to prepare the paste-like negative electrode mixture used in the formation of the negative electrode of a lithium-ion secondary battery, the required solvent amount becomes enormous, which is therefore undesirable.
[0104] [Process D]
[0105] In step D, the raw carbon powder obtained by pulverizing the heat-treated raw carbon composition is graphitized to obtain graphite powder. Specifically, the raw carbon powder is further heat-treated to remove volatile components, and then dehydrated and thermally decomposed to carry out a solid-phase graphitization reaction. By performing this graphitization treatment, a stable quality artificial graphite material can be obtained.
[0106] Examples of graphitization methods include calcination to remove volatile components from the raw carbon powder to obtain calcined coke, followed by carbonization, and then heat treatment for graphitization. Calcination and carbonization can be performed as needed or omitted. Even if calcination and carbonization are omitted in the graphitization process, the physical properties of the final manufactured artificial graphite material are essentially unaffected.
[0107] Calcination can be exemplified by a heat treatment method in an inert gas atmosphere such as nitrogen, argon, or helium, where the maximum temperature reaches 500–1500°C, preferably 900–1200°C, and the holding time at the maximum temperature is 0–10 hours.
[0108] As a carbonization process, for example, a method of heat treatment in an inert gas atmosphere such as nitrogen, argon, or helium, with a maximum temperature of 500–1500°C, preferably 900–1500°C, and a holding time of 0–10 hours at the maximum temperature can be described.
[0109] As a graphitization process, examples include heating treatment in an atmosphere of inert gases such as nitrogen, argon, or helium, with a maximum temperature of 2500–3200°C, preferably 2800–3200°C, and a holding time of 0–100 hours at the maximum temperature. Alternatively, graphitization can be carried out by sealing the raw carbon powder in a graphite crucible and using a graphitization furnace such as an Archeson furnace or an LWG furnace.
[0110] [Process E]
[0111] In step E, the method for pulverizing the graphite powder obtained by graphitizing the raw carbon powder can be any known method such as an air jet mill, and there is no particular limitation.
[0112] A lithium-ion secondary battery having an artificial graphite material negative electrode obtained by the manufacturing method of artificial graphite material for lithium-ion secondary battery according to this embodiment becomes a battery whose discharge capacity is not easily degraded even when repeatedly charged and discharged at a low temperature of -10°C.
[0113] <<Negative Electrode for Lithium-ion Secondary Batteries>>
[0114] Next, the negative electrode for a lithium-ion secondary battery according to this embodiment will be described. The negative electrode for a lithium-ion secondary battery according to this embodiment includes a carbon material containing artificial graphite material obtained by the manufacturing method of the above embodiment, a binder, and conductive additives as needed. The negative electrode for a lithium-ion secondary battery according to this embodiment only needs to contain artificial graphite material obtained by the manufacturing method of the above embodiment. As needed, the carbon material may include not only the artificial graphite material obtained by the manufacturing method of the above embodiment, but may also include one or more known graphite materials or amorphous carbon materials.
[0115] As well-known graphite materials, examples include artificial graphite materials other than the artificial graphite material described in this embodiment, as well as natural graphite-based materials. Furthermore, as amorphous carbon materials, examples include well-known easily graphitizable carbon materials and difficult-to-graphitize carbon materials.
[0116] As natural graphite-based materials, examples include graphite-like substances produced naturally, materials obtained by purifying the aforementioned graphite-like substances, materials that are then shaped into spheres (including those that have undergone mechanical and chemical treatment), materials obtained by covering the surface of high-purity products and spheres with additional carbon (such as asphalt coatings, CVD coatings, etc.), and materials that have undergone plasma treatment.
[0117] In this embodiment, the shape of artificial graphite materials other than artificial graphite materials, natural graphite-based materials, and amorphous carbon materials is not particularly limited. For example, they can be flake-shaped, spherical, or block-shaped.
[0118] As the carbon material, in addition to the artificial graphite material obtained by the manufacturing method of the above embodiments, if the mixture also includes graphite materials other than the artificial graphite material obtained by the manufacturing method of the above embodiments, the mixing ratio can be set to any ratio. When including graphite materials other than the artificial graphite material obtained by the manufacturing method of the above embodiments, it is preferable to include 20% by mass or more of the artificial graphite material obtained by the manufacturing method of the above embodiments, more preferably 30% by mass or more, and even more preferably 50% by mass or more.
[0119] As a binder, known binders used in the negative electrode of lithium-ion secondary batteries can be used, such as carboxymethyl cellulose (CMC), polyvinylidene fluoride, polytetrafluoroethylene, SBR (styrene-butadiene rubber), etc., used alone, or a mixture of two or more. The binder content in the negative electrode mixture is preferably set to about 1 to 30 parts by weight relative to 100 parts by weight of graphite material, which can be appropriately set according to the needs in the design of lithium-ion secondary batteries.
[0120] As a conductive additive, known conductive additives used in the negative electrode of lithium-ion secondary batteries can be used, such as carbon black, graphite, acetylene black, conductive polymers such as indium tin oxide, polyaniline, polythiophene, and polyphenylene oxide, which exhibit conductivity, can be used alone, or two or more can be mixed. The amount of conductive additive used is preferably set to 1 to 15 parts by weight relative to 100 parts by weight of graphite material, which can be appropriately set according to the needs in the design of lithium-ion secondary batteries.
[0121] As for the method of manufacturing the negative electrode for a lithium-ion secondary battery according to this embodiment, there is no particular limitation as long as the method utilizes a carbon material containing artificial graphite material obtained by the manufacturing method of the above embodiment, and a known manufacturing method can be used. The manufacturing method of the negative electrode for a lithium-ion secondary battery according to this embodiment involves press-forming a carbon material containing artificial graphite material obtained by the manufacturing method of the above embodiment. For example, a method can be listed that involves manufacturing a mixture comprising a carbon material containing artificial graphite material obtained by the manufacturing method of the above embodiment, a binder, a conductive additive as needed, and a solvent, i.e., a negative electrode mixture, and then press-forming the negative electrode mixture to a predetermined size.
[0122] As the solvent used in the negative electrode mixture, known solvents used in the negative electrodes of lithium-ion secondary batteries can be used. Specifically, for example, organic solvents such as dimethylformamide, N-methylpyrrolidone, isopropanol, and toluene, solvents such as water, or a mixture of two or more can be used alone.
[0123] As a method for mixing graphite material, binder, conductive additives (if desired), and organic solvent in the manufacture of negative electrode mixtures, known apparatuses such as screw kneaders, ribbon mixers, universal mixers, and planetary mixers can be used. The negative electrode mixture can be pressurized using methods such as roller pressing or press pressing. Pressurization of the negative electrode mixture is preferably performed at a pressure of approximately 100–300 MPa.
[0124] The negative electrode for a lithium-ion secondary battery according to this embodiment can be manufactured, for example, by the method described below. Specifically, a slurry or paste-like negative electrode mixture is prepared by mixing graphite material containing artificial graphite material obtained through the manufacturing method described above, a binder, conductive additives as needed, and a solvent using a known method. Then, the slurry-like negative electrode mixture is coated onto a negative electrode current collector such as copper foil and dried to form a sheet, granules, or other shape. Finally, the dried layer formed from the negative electrode mixture is calendered and cut to a specified size.
[0125] There are no particular limitations on the method of coating the slurry-like negative electrode mixture onto the negative electrode current collector. For example, known methods such as metal mask printing, electrostatic coating, dip coating, spray coating, roller coating, doctor blade coating, gravure coating, screen printing, and mold coating can be used.
[0126] The negative electrode compound coated on the negative electrode current collector is preferably calendered using a flatbed press, calendering rolls, or similar methods. The dried layer of negative electrode compound formed on the negative electrode current collector can be integrated with the negative electrode current collector by known methods such as using rollers, presses, or combinations thereof.
[0127] As for the material used as the negative electrode current collector, any material that does not form an alloy with lithium can be used without particular restrictions. Specifically, examples of materials that can be used as negative electrode current collectors include copper, nickel, titanium, and stainless steel. Regarding the shape of the negative electrode current collector, there are also no particular restrictions. Specifically, examples of shapes that can be used as negative electrode current collectors include foil, perforated foil, mesh, and strip-shaped forms.
[0128] In addition, porous materials such as porous metals (foamed metals) and carbon paper can also be used as negative electrode current collectors.
[0129] <<Lithium-ion Secondary Batteries>>
[0130] Next, the lithium-ion secondary battery of this embodiment will be described. Figure 1 This is a schematic cross-sectional view showing an example of a lithium-ion secondary battery according to this embodiment. Figure 1The lithium-ion secondary battery 10 shown has a negative electrode 11 integrated with the negative current collector 12 and a positive electrode 13 integrated with the positive current collector 14. Figure 1 In the lithium-ion secondary battery 10 shown, the negative electrode of this embodiment is used as the negative electrode 11. The negative electrode 11 and the positive electrode 13 are arranged opposite each other through a separator 15. Figure 1 In the diagram, symbol 16 represents an aluminum laminated outer packaging. Electrolyte is injected inside the aluminum laminated outer packaging 16.
[0131] The positive electrode 13 comprises an active material, a binder, and conductive additives as needed. As the active material, known active materials used in positive electrodes for lithium-ion secondary batteries can be used, including metal compounds, metal oxides, metal sulfides, or conductive polymers capable of doping or intercalating lithium ions. Specifically, examples of active materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), and composite oxides (LiCo... X Ni Y Mn Z O2, X+Y+Z=1), lithium vanadium compounds, V2O5, V6O 13 Conductive polymers such as VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), polyacetylene, polyaniline, polypyrrole, polythiophene, polybenzoxene, porous carbon, and mixtures thereof.
[0132] As the adhesive, the same adhesive used in the negative electrode 11 described above can be used. As the conductive additive, the same conductive additive used in the negative electrode 11 described above can be used.
[0133] As the positive current collector 14, a valve metal or its alloy thereof that forms a passive film on its surface through anodic oxidation in the electrolyte is preferably used. Specifically, Al, Ti, Zr, Hf, Nb, Ta, and alloys containing these metals can be used. In particular, Al and its alloys are preferred due to their lightweight and high energy density.
[0134] As the separator 15, for example, nonwoven fabric, cloth, microporous membrane, or a combination thereof with polyolefins such as polyethylene and polypropylene as the main components can be used. It should be noted that in the case of a lithium-ion secondary battery where the positive and negative electrodes are not in direct contact, a separator is not required.
[0135] As the electrolyte and electrolyte used in the lithium-ion secondary battery 10, known organic electrolytes, inorganic solid electrolytes, and polymeric solid electrolytes used in lithium-ion secondary batteries can be used. From the viewpoint of conductivity, organic electrolytes are preferred as the electrolyte.
[0136] Examples of organic electrolytes include dibutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, ethylene glycol phenyl ether, etc.; amides such as N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, etc.; sulfur-containing compounds such as dimethyl sulfoxide and sulfolane; methyl ethyl ketone; and so on. The organic solvents used include dialkyl ketones such as isobutyl ketone, cyclic ethers such as tetrahydrofuran and 2-methoxytetrahydrofuran, cyclic carbonates such as ethylene carbonate, butyl carbonate, propylene carbonate, and vinylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate, cyclic carbonates such as γ-butyrolactone and γ-valerolactone, chain carbonates such as methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate, N-methyl-2-pyrrolidone, acetonitrile, and nitromethane. These organic electrolytes can be used alone or in combination of two or more.
[0137] Various known lithium salts can be used as electrolytes. For example, lithium salts such as LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCl, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, and LiN(C2F5SO2)2 can be listed.
[0138] Examples of high molecular weight solid electrolytes include polyethylene oxide derivatives and polymers containing such derivatives, polypropylene oxide derivatives and polymers containing such derivatives, phosphate ester polymers, polycarbonate derivatives and polymers containing such derivatives, etc.
[0139] The lithium-ion secondary battery 10 of this embodiment, having a negative electrode 11 comprising the artificial graphite material of this embodiment, is not prone to capacity degradation even after repeated charge-discharge cycles at temperatures below -10°C. Therefore, the lithium-ion secondary battery 10 of this embodiment is preferably used for industrial applications such as hybrid electric vehicles, plug-in hybrid electric vehicles, electric vehicles, and power storage for public infrastructure systems.
[0140] It should be noted that, as long as the lithium-ion secondary battery of the present invention uses the negative electrode of the present invention, the selection of necessary components in the battery structure other than the negative electrode is not restricted in any way.
[0141] Specifically, the structure of the lithium-ion secondary battery of the present invention is not limited to Figure 1 The lithium-ion secondary battery 10 shown is illustrated.
[0142] As for the method of manufacturing the lithium-ion secondary battery of this embodiment, there is no particular limitation as long as the method of manufacturing the negative electrode for the lithium-ion secondary battery obtained by the method of manufacturing the negative electrode for the lithium-ion secondary battery of the above embodiment is used, and a known manufacturing method can be used. The method of manufacturing the lithium-ion secondary battery of this embodiment includes the step of arranging the negative electrode and the positive electrode obtained by the method of manufacturing the negative electrode for the lithium-ion secondary battery of the above embodiment opposite to each other through a separator. Preferably, the method includes the following steps: integrating the negative electrode and the negative electrode current collector obtained by the method of manufacturing the negative electrode for the lithium-ion secondary battery of the above embodiment, integrating the positive electrode and the positive electrode current collector, and arranging the negative electrode integrated with the negative electrode current collector and the positive electrode integrated with the positive electrode current collector opposite to each other through a separator. The single-layer electrode body, which is arranged opposite to the negative electrode integrated with the negative electrode current collector and the positive electrode integrated with the positive electrode current collector through a separator, is housed in an outer packaging body, and electrolyte is injected into the interior of the outer packaging body to obtain the lithium-ion secondary battery of this embodiment.
[0143] For example, a lithium-ion secondary battery can be structured by inserting a spiral electrode assembly, formed into strips of positive and negative electrodes and wound into a vortex shape by a separator, into a battery casing and then sealing it. Alternatively, a lithium-ion secondary battery can be structured by sealing a stacked electrode assembly, formed into flat plates of positive and negative electrodes and sequentially stacked by a separator, into an outer packaging body.
[0144] The lithium-ion secondary battery of the present invention can be used as, for example, a paper-type battery, a button-type battery, a coin-type battery, a stacked battery, a cylindrical battery, a square battery, etc.
[0145] Example
[0146] The present invention will be further described in detail below through embodiments and comparative examples. It should be noted that the present invention is not limited to the following embodiments.
[0147] Manufacturing of Artificial Graphite Materials
[0148] (Example 1)
[0149] Manufacturing of Feedstock Compositions
[0150] The substance obtained by vacuum distillation and further hydrodesulfurization of residual oil from atmospheric distillation (sulfur content 380 ppm by mass, density 0.83 g / cm³ at 15°C) 3Fluidized catalytic cracking was carried out at a reaction temperature of 530℃, a total pressure of 0.23 MPa, a catalyst / oil ratio of 13, and a catalytic time of 7 seconds to obtain fluidized catalytic cracking residue oil. A platinum-supported material on a silica / alumina catalyst was used as the catalyst. It should be noted that "sulfur content" refers to the value measured according to JIS K 2541.
[0151] Furthermore, after adding an equal volume of n-heptane to the fluidized catalytic cracking residue obtained through such operation and mixing, selective extraction with dimethylformamide is performed to separate aromatic and saturated components.
[0152] Furthermore, the residual oil from atmospheric distillation (sulfur content 0.35% by mass, density 0.92 g / cm³ at 15°C) 3 Vacuum distillation was carried out at a furnace outlet temperature of 350℃ and a pressure of 1.3 kPa to obtain a vacuum distillation residue with an initial boiling point of 410℃, a bituminous content of 9% by mass, a saturated content of 61% by mass, a sulfur content of 0.1% by mass, and a nitrogen content of 0.3% by mass. An equal volume of n-heptane was added to this vacuum distillation residue, and after mixing, selective extraction was performed using dimethylformamide to separate aromatic and saturated components. It should be noted that "nitrogen content" refers to the value determined according to JIS K 2609. Furthermore, "saturated content" and "bituminous content" refer to the values determined using thin-layer chromatography.
[0153] The fluidized bed catalytic cracking residue, the saturated components of the fluidized bed catalytic cracking residue, and the saturated components of the vacuum distillation residue obtained in this manner were mixed in a mass ratio of 43:50:7 to obtain the feedstock composition of Example 1. The n-alkane content and aromatic index fa of the feedstock composition of Example 1 were determined by the method shown below. The results are shown in Table 1. Furthermore, the n-alkane content and aromatic index fa of the feedstock compositions obtained in Examples 2-5 and Comparative Examples 4-8 described later were also determined by the same method. The results are shown in Table 1.
[0154] (Content of n-chain alkanes)
[0155] The content of n-alkanes in a feedstock oil composition is determined by gas chromatography equipped with a capillary column. Specifically, after identification using a standard reference for n-alkanes, a sample of non-aromatic components separated by elution chromatography is passed through a capillary column for determination. The content (mass %) is calculated from this determination, based on the total mass of the feedstock oil composition.
[0156] (Aromatic Index fa)
[0157] The aromatic index fa of the feedstock oil composition was determined using the Knight's method. Specifically, the carbon distribution was used as a metric. 13The C-NMR spectrum of aromatic carbons is divided into three components (A1, A2, A3). A1 represents the number of carbons within the aromatic ring (half the number of substituted and unsubstituted aromatic carbons). 13 The peak at approximately 40–60 ppm in C-NMR indicates that A2 represents the unsubstituted remaining half of the aromatic carbon (equivalent to…). 13 The peak at approximately 60–80 ppm in C-NMR is A3, which represents an aliphatic carbon number (equivalent to…). 13 The C-NMR peaks are approximately 130–190 ppm. The aromatic index fa is calculated using A1, A2, and A3 by fa = (A1 + A2) / (A1 + A2 + A3).
[0158] Process A
[0159] Next, the raw material oil composition of Example 1 was placed in a test tube for coking treatment. It was heat-treated at 500°C under normal pressure for 3 hours to coke and obtain the raw material carbon composition of Example 1.
[0160] Process B
[0161] The raw material carbon composition of Example 1 was heated at 550°C under a nitrogen gas flow to obtain the heat-treated raw material carbon composition of Example 1.
[0162] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 550°C is set to 1 hour, the holding time at 550°C is set to 1 hour, the cooling time from 550°C to 400°C is set to 1 hour, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0163] Process C
[0164] The heat-treated raw carbon composition obtained in Example 1 was pulverized using a hammer mill to obtain raw carbon powder of Example 1, with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device. The volatile matter and true density of the obtained raw carbon powder were determined using the method shown below. The results are shown in Table 1. It should be noted that the volatile matter and true density of the raw carbon powder obtained in Examples 2-5, 9-13, and Comparative Examples 1-16 were also determined using the same method. The results are shown in Tables 1-2.
[0165] (Determination of volatile components)
[0166] The volatile components [mass fraction (%)] of the raw material carbon powder were determined according to "7.2 Vertical tubular electric furnace method" and "b) coke case" in "7. Quantitative method of volatile components" of JIS M 8812 (2004) "Coal and coke - Industrial analysis method".
[0167] (Determination of true density)
[0168] True density of raw carbon powder [g / cm³] 3 The density is determined according to the "7.3 True Density Test Method" of "7. Density and Porosity Test Method" in "Coke-type Test Methods" of JIS K 2151 (2004).
[0169] Process D
[0170] The raw carbon powder from Example 1 was placed into a graphite crucible, which was then buried in the heating material, insulation material, and filler coke within an Archeson electric furnace, and graphitized at 2950°C. As part of the graphitization process, the heating time from room temperature to 2950°C was set to 130 hours, the holding time at 2950°C was set to 8 hours, and the powder was removed after cooling for 25 days to obtain graphite powder.
[0171] Process E
[0172] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 1.
[0173] (Calculation of the size L(112) of the microcrystal)
[0174] In Example 1, 10% by mass of a Si standard sample was mixed with the artificial graphite material used as the negative electrode of a lithium-ion secondary battery. The sample was placed in a glass sample holder (window frame size 16mm × 20mm, depth 0.2mm) and the crystallite size L (112) was calculated by wide-angle X-ray diffraction according to JIS R7651 (2007). A Rigaku Corporation ULTIMA IV X-ray diffraction apparatus was used as the X-ray source, employing CuKα rays (with a Ni Kβ filter). The applied voltage and current to the X-ray tube were set to 40kV and 40mA, respectively.
[0175] The obtained diffraction patterns were analyzed according to the method in JIS R 7651 (2007). Specifically, after smoothing and background removal of the measurement data, absorption correction, polarization correction, and Lorentz correction were performed. Then, using the peak position and width of the (422) diffraction line of the Si standard sample, the (112) diffraction line of the artificial graphite material used as the negative electrode of the lithium-ion secondary battery was corrected, and the crystallite size L(112) was calculated. It should be noted that the crystallite size was calculated from the half-width of the corrected peak using the following Scherrer formula. The measurement and analysis were each performed three times, and the average value was set as L(112).
[0176] L=K×λ / (β×cosθB) ------Scherrer's formula
[0177] Where L: Crystal size (nm)
[0178] K: Shape factor constant (=1.0)
[0179] λ: Wavelength of X-rays (=0.15406nm)
[0180] θ: Bragg angle (corrected diffraction angle)
[0181] β: True half-width (correction value)
[0182] (Determination of nitrogen adsorption specific surface area S(BET))
[0183] The nitrogen adsorption specific surface area of the artificial graphite material used as the negative electrode of the lithium-ion secondary battery in Example 1 was measured and calculated using a specific surface area measuring apparatus (BELSO RPminiII) manufactured by MicrotracBEL Co., Ltd., according to JIS Z 8830 (2013), "Method for determining the specific surface area of powders (solids) by gas adsorption". It should be noted that the pre-drying of the artificial graphite material was carried out at 300°C under reduced pressure for 3 hours. Afterwards, the specific surface area value (m²) was calculated using the nitrogen adsorption BET multi-point method based on gas flow. 2 / g).
[0184] (Measurement of ESR signal strength I(4.8K) and calculation of I(4.8K) / S(BET))
[0185] Approximately 1.5 mg of the artificial graphite material from the lithium-ion secondary battery of Example 1 was placed in a sample tube. After evacuation using a rotary pump, He gas was introduced into the sample tube for ESR measurement. The ESR apparatus, microwave frequency counter, gaussmeter, and cryostat were BRUKER ESP350E, HEWLETT PACKARD HP5351P, BRUKER ER035M, and OXFORD ESR910, respectively. An X-band microwave (9.60 GHz) was used, with a strength of 1 mW, a central magnetic field of 3412 G, and a magnetic field modulation of 100 kHz. The measurement temperature was 4.8 K, and the absorption intensity (I4.8 K) was calculated and shown in Table 1. The signal intensity (spins / g) was obtained by quadratically integrating the ESR spectrum and correcting it with a standard substance. It should be noted that the carbon radical-originating peak observed in the electron spin resonance method using microwaves in the X-band region appeared near g = 2.0 in the negative electrode materials of both the embodiment and the comparative example. The ratio of the obtained signal intensity I (4.8 K) to the nitrogen adsorption specific surface area S (BET), I (4.8 K) / S (BET), was calculated (spins / m). 2 ).
[0186] The crystallite size L(112), nitrogen adsorption specific surface area S(BET), ESR signal intensity I(4.8K), and ratio I(4.8K) / S(BET) of the obtained artificial graphite material for lithium-ion secondary battery anodes are shown in Table 1. It should be noted that the crystallite size L(112), nitrogen adsorption specific surface area S(BET), ESR signal intensity I(4.8K), and ratio I(4.8K) / S(BET) of the artificial graphite materials for lithium-ion secondary battery anodes in Examples 2-5 and Comparative Examples 1-8 were also determined using the same method. The results are shown in Table 1.
[0187] (Example 2)
[0188] Manufacturing of Feedstock Compositions
[0189] Atmospheric distillation residue with a sulfur content of 3.1% by mass was hydrodesulfurized in the presence of a catalyst, with a hydrocracking rate of less than 25%, to obtain hydrodesulfurized oil. The hydrodesulfurization conditions were set as follows: total pressure 18 MPa, hydrogen partial pressure 16 MPa, and temperature 380 °C.
[0190] The hydrodesulfurized oil obtained in this manner and the fluidized catalytic cracking residue obtained in Example 1 were mixed at a mass ratio of 5:95 to obtain the feedstock composition of Example 2.
[0191] Process A
[0192] The feedstock oil composition of Example 2 was coked using the same coking process as in Example 1 to obtain a feedstock carbon composition.
[0193] Process B
[0194] The obtained raw material carbon composition was heated at 700°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0195] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 700°C is set to 2 hours, the holding time at 700°C is set to 1 hour, the cooling time from 700°C to 400°C is set to 2 hours, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0196] Process C
[0197] The obtained heat-treated raw material carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 2.
[0198] Process D
[0199] The raw carbon powder from Example 2 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0200] Process E
[0201] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 2.
[0202] (Example 3)
[0203] Manufacturing of Feedstock Compositions
[0204] The saturated components of the fluidized catalytic cracking residue obtained in Example 1 and the aromatic components of the fluidized catalytic cracking residue were mixed in a mass ratio of 70:30 to obtain the feedstock composition of Example 3.
[0205] Process A
[0206] The feedstock oil composition of Example 3 was coked using the same coking process as in Example 1 to obtain a feedstock carbon composition.
[0207] Process B
[0208] The obtained raw material carbon composition was heated at 600°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition. As a heat treatment method, the following treatment was performed: the heating time from room temperature to 600°C was set to 1 hour and 30 minutes, the holding time at 600°C was set to 1 hour, the cooling time from 600°C to 400°C was set to 1 hour and 30 minutes, and after reaching 400°C, cooling was performed for 4 hours while continuing the nitrogen gas flow.
[0209] Process C
[0210] The obtained heat-treated raw material carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 3.
[0211] Process D
[0212] The raw carbon powder of Example 3 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0213] Process E
[0214] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 3.
[0215] (Example 4)
[0216] Manufacturing of Feedstock Compositions
[0217] The saturated components of the vacuum distillation residue oil obtained in Example 1 and the aromatic components of the fluidized catalytic cracking residue oil obtained in Example 1 were mixed at a mass ratio of 30:70 to obtain the feedstock oil composition of Example 4.
[0218] Process A
[0219] The feedstock oil composition of Example 4 was coked using the same coking process as in Example 1 to obtain the feedstock carbon composition.
[0220] Process B
[0221] The obtained raw material carbon composition was heated at 500°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0222] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 500°C is set to 1 hour, the holding time at 500°C is set to 1 hour, the cooling time from 500°C to 400°C is set to 1 hour, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0223] Process C
[0224] The obtained heat-treated raw material carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 4.
[0225] Process D
[0226] The raw carbon powder from Example 4 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0227] Process E
[0228] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 4.
[0229] (Example 5)
[0230] Manufacturing of Feedstock Compositions
[0231] The saturated components of the fluidized catalytic cracking residue obtained in Example 1, the aromatic components of the fluidized catalytic cracking residue obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 20:20:60 to obtain the feedstock composition of Example 5.
[0232] Process A
[0233] The feedstock oil composition of Example 5 was coked using the same coking process as in Example 1 to obtain a feedstock carbon composition.
[0234] Process B
[0235] The obtained raw material carbon composition was heated at 500°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0236] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 500°C is set to 1 hour, the holding time at 500°C is set to 1 hour, the cooling time from 500°C to 400°C is set to 1 hour, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0237] Process C
[0238] The obtained heat-treated raw material carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 5.
[0239] Process D
[0240] The raw carbon powder from Example 5 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0241] Process E
[0242] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 5.
[0243] (Comparative Example 1)
[0244] Process A
[0245] The same procedure as in Example 1 was followed to obtain the raw material carbon composition.
[0246] Low-Temperature Heat Treatment Process
[0247] The raw material carbon composition of Example 1 was heated at 400°C under a nitrogen gas flow to obtain the heat-treated raw material carbon composition of Comparative Example 1.
[0248] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 400°C is set to 1 hour, the holding time at 400°C is set to 1 hour, and then the temperature is cooled for 4 hours while the nitrogen gas flow continues.
[0249] Process C
[0250] The heat-treated raw carbon composition of Comparative Example 1 was pulverized using a hammer mill to obtain raw carbon powder, with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0251] Process D
[0252] The raw carbon powder of Comparative Example 1 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0253] Process E
[0254] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for the negative electrode of a lithium-ion secondary battery of Comparative Example 1.
[0255] (Comparative Example 2)
[0256] Process A
[0257] The same procedure as in Example 1 was followed to obtain the raw material carbon composition.
[0258] High-Temperature Heat Treatment Process
[0259] The raw material carbon composition of Example 1 was heated at 750°C under a nitrogen gas flow to obtain the heat-treated raw material carbon composition of Comparative Example 2.
[0260] As a heat treatment method, the following process is performed: the heating time from room temperature to 750°C is set to 2 hours, the holding time at 750°C is set to 1 hour, the cooling time from 750°C to 400°C is set to 2 hours, and after reaching 400°C, cooling is performed while continuing to flow nitrogen for 4 hours. This is followed by a process of cooling while continuing to flow nitrogen for 4 hours.
[0261] Process C
[0262] The heat-treated raw carbon composition of Comparative Example 2 was pulverized using a hammer mill to obtain the raw carbon powder of Comparative Example 2, with the average particle size measured by a laser diffraction particle size distribution measuring device being in the range of 19.5 to 20.5 μm.
[0263] Process D
[0264] The raw carbon powder of Comparative Example 2 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0265] Process E
[0266] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for the negative electrode of a lithium-ion secondary battery of Comparative Example 2.
[0267] (Comparative Example 3)
[0268] Process A
[0269] The same procedure as in Example 1 was followed to obtain the raw material carbon composition.
[0270] Heat Treatment Process
[0271] In the manufacturing method of the artificial graphite material for the negative electrode of a lithium-ion secondary battery in Comparative Example 3, no heat treatment of the raw material carbon composition was performed.
[0272] Process C
[0273] The raw carbon composition of Example 1 was pulverized using a hammer mill to obtain raw carbon powder, with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0274] Process D
[0275] The raw carbon powder obtained in this way was graphitized using the same method as in Example 1 to obtain graphite powder.
[0276] Process E
[0277] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 3.
[0278] (Comparative Example 4)
[0279] Manufacturing of Feedstock Compositions
[0280] The aromatic components of the fluidized catalytic cracking residue obtained in Example 1, the saturated components of the fluidized catalytic cracking residue obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 15:20:65 to obtain the feedstock composition of Comparative Example 4.
[0281] Process A
[0282] The feedstock oil composition of Comparative Example 4 was coked by coking treatment in the same manner as in Example 1 to obtain a feedstock carbon composition.
[0283] Process B
[0284] The obtained raw material carbon composition was heated at 500°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0285] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 500°C is set to 1 hour, the holding time at 500°C is set to 1 hour, the cooling time from 500°C to 400°C is set to 1 hour, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0286] Process C
[0287] The obtained heat-treated raw carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device to obtain the raw carbon powder of Comparative Example 4.
[0288] Process D
[0289] The raw carbon powder of Comparative Example 4 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0290] Process E
[0291] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 4.
[0292] (Comparative Example 5)
[0293] Manufacturing of Feedstock Compositions
[0294] The aromatic components of the fluidized catalytic cracking residue obtained in Example 1 and the saturated components of the fluidized catalytic cracking residue obtained in Example 1 were mixed in a mass ratio of 50:50 to obtain the feedstock composition of Comparative Example 5.
[0295] Process A
[0296] The feedstock oil composition of Comparative Example 5 was coked by coking treatment in the same manner as in Example 1 to obtain a feedstock carbon composition.
[0297] Process B
[0298] The obtained raw material carbon composition was heated at 700°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0299] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 700°C is set to 2 hours, the holding time at 700°C is set to 1 hour, the cooling time from 700°C to 400°C is set to 2 hours, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0300] Process C
[0301] The obtained heat-treated raw carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw carbon powder of Comparative Example 5.
[0302] Process D
[0303] The raw carbon powder of Comparative Example 5 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0304] Process E
[0305] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 5.
[0306] (Comparative Example 6)
[0307] Manufacturing of Feedstock Compositions
[0308] The saturated components of the vacuum distillation residue obtained in Example 1 and the aromatic components of the fluidized catalytic cracking residue obtained in Example 1 were mixed at a mass ratio of 15:85 to obtain the feedstock composition of Comparative Example 6.
[0309] Process A
[0310] The feedstock oil composition of Comparative Example 6 was coked by coking treatment in the same manner as in Example 1 to obtain a feedstock carbon composition.
[0311] Process B
[0312] The obtained raw material carbon composition was heated at 600°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0313] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 600°C is set to 1 hour and 30 minutes, the holding time at 600°C is set to 1 hour, the cooling time from 600°C to 400°C is set to 1 hour and 30 minutes, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0314] Process C
[0315] The obtained heat-treated raw carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw carbon powder of Comparative Example 6.
[0316] Process D
[0317] The raw carbon powder of Comparative Example 6 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0318] Process E
[0319] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 6.
[0320] (Comparative Example 7)
[0321] Manufacturing of Feedstock Compositions
[0322] The saturated components of the vacuum distillation residue obtained in Example 1, the aromatic components of the fluidized catalytic cracking residue obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 4:91:5 to obtain the feedstock composition of Comparative Example 7.
[0323] Process A
[0324] The feedstock oil composition of Comparative Example 7 was coked by coking treatment in the same manner as in Example 1 to obtain a feedstock carbon composition.
[0325] Process B
[0326] The obtained raw material carbon composition was heated at 650°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0327] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 650°C is set to 1 hour and 30 minutes, the holding time at 650°C is set to 1 hour, the cooling time from 650°C to 400°C is set to 1 hour and 30 minutes, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0328] Process C
[0329] The obtained heat-treated raw carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw carbon powder of Comparative Example 7.
[0330] Process D
[0331] The raw carbon powder of Comparative Example 7 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0332] Process E
[0333] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 7.
[0334] (Comparative Example 8)
[0335] Manufacturing of Feedstock Compositions
[0336] The aromatic components of the fluidized catalytic cracking residue obtained in Example 1 and the hydrodesulfurized oil obtained in Example 2 were mixed at a mass ratio of 15:85 to obtain the feedstock composition of Comparative Example 8.
[0337] Process A
[0338] The feedstock oil composition of Comparative Example 8 was coked by coking treatment in the same manner as in Example 1 to obtain a feedstock carbon composition.
[0339] Process B
[0340] The obtained raw material carbon composition was heated at 550°C under a nitrogen gas flow to obtain a heat-treated raw material carbon composition.
[0341] As a heat treatment method, the following treatment is performed: the heating time from room temperature to 550°C is set to 1 hour, the holding time at 550°C is set to 1 hour, the cooling time from 550°C to 400°C is set to 1 hour, and after 400°C, the temperature is cooled for 4 hours while continuing to flow nitrogen.
[0342] Process C
[0343] The obtained heat-treated raw carbon composition was pulverized using a hammer mill with an average particle size ranging from 19.5 to 20.5 μm as determined by a laser diffraction particle size distribution measuring device to obtain the raw carbon powder of Comparative Example 8.
[0344] Process D
[0345] The raw carbon powder of Comparative Example 8 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0346] Process E
[0347] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 9.5 to 10.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 8.
[0348] (Example 6)
[0349] The artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 were mixed in a mass ratio of 50:50 to form a mixture, and the artificial graphite material for lithium-ion secondary battery negative electrode of Example 6 was formed from the mixture.
[0350] (Example 7)
[0351] The artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 were mixed in a mass ratio of 30:70 to form a mixture, and the artificial graphite material for lithium-ion secondary battery negative electrode of Example 7 was formed from the mixture.
[0352] (Example 8)
[0353] The artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 were mixed in a mass ratio of 20:80 to form a mixture, and the artificial graphite material for the negative electrode of a lithium-ion secondary battery of Example 8 was formed from the mixture.
[0354] <Evaluation of the battery manufacturing process (1)>
[0355] The following method was used to create Figure 1 The lithium-ion secondary battery 10 shown is used as an evaluation battery. The components shown below are used as the negative electrode 11, negative electrode current collector 12, positive electrode 13, positive electrode current collector 14, and separator 15, respectively.
[0356] (Negative electrode 11, negative current collector 12)
[0357] An aqueous solution of carboxymethyl cellulose (CMC (BSH-6 manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.)) as a binder, adjusted to a concentration of 1.5% by mass, and an aqueous solution of styrene-butadiene rubber (SBR) dispersed as a binder at a concentration of 48% by mass were mixed in a ratio of 98:1:1 based on the mass ratio of solid components to obtain a paste-like negative electrode mixture.
[0358] The obtained negative electrode mixture is coated on one side of a copper foil with a thickness of 18 μm, which serves as the negative electrode current collector 12. After drying and rolling, a negative electrode sheet is obtained in which a layer formed by the negative electrode mixture, i.e., the negative electrode 11, is formed on the negative electrode current collector 12.
[0359] The coating amount of the negative electrode agent per unit area in the negative electrode sheet is approximately 9.4 mg / cm³ based on the mass of the graphite material. 2 Adjustments will be made in this manner.
[0360] Next, the negative electrode sheet is cut to a width of 32 mm and a length of 52 mm. Then, a portion of the negative electrode 11 is scraped off in a direction perpendicular to the length of the sheet, exposing the negative electrode current collector 12, which serves as the negative electrode lead plate.
[0361] (Positive electrode 13, positive current collector 14)
[0362] Lithium cobalt oxide (LiCoO2) with an average particle size of 10 μm (CELLSEED C10N manufactured by Nippon Chemical Industry Co., Ltd.), polyvinylidene fluoride (KF#1120 manufactured by KUREHA CORPORATION) as a binder, and acetylene black (DENKA BLACK manufactured by Denka Co., Ltd.) as a conductive additive were mixed in a mass ratio of 89:6:5. N-methyl-2-pyrrolidone was added as a solvent and the mixture was kneaded to obtain a paste-like positive electrode mixture.
[0363] The obtained positive electrode mixture is coated on one side of an aluminum foil with a thickness of 30 μm, which serves as the positive electrode current collector 14. After drying and rolling, a positive electrode sheet with a layer formed by the positive electrode mixture, namely the positive electrode 13, is obtained on the positive electrode current collector 14.
[0364] The coating amount of the positive electrode compound per unit area in the positive electrode sheet is approximately 20 mg / cm² based on the mass of lithium cobalt oxide. 2 Adjustments will be made in this manner.
[0365] Next, the positive electrode sheet is cut to a width of 30 mm and a length of 50 mm. Then, a portion of the positive electrode 13 is scraped off in a direction perpendicular to the length of the sheet, exposing the positive current collector 14, which serves as the positive electrode lead plate.
[0366] (Septum 15)
[0367] As the diaphragm 15, a cellulose-based nonwoven fabric (TF40-50 manufactured by Japan Kotaka Paper Co., Ltd.) was used. For the fabrication... Figure 1 The lithium-ion secondary battery 10 shown is first subjected to drying of the negative electrode sheet (which integrates the negative electrode 11 with the negative electrode current collector 12 and the negative electrode lead plate), the positive electrode sheet (which integrates the positive electrode 13 with the positive electrode current collector 14 and the positive electrode lead plate), the separator 15, and other components used in the lithium-ion secondary battery 10. Specifically, the negative electrode sheet and the positive electrode sheet are dried at 120°C under reduced pressure for at least 12 hours. Furthermore, the separator 15 and other components are dried at 70°C under reduced pressure for at least 12 hours.
[0368] Next, the dried negative electrode sheet, positive electrode sheet, separator 15, and other components are assembled in an argon-circulating glove box with a dew point controlled below -60°C. This yields the following... Figure 1As shown, the positive electrode 13 and the negative electrode 11 are stacked opposite each other through a separator 15 and fixed with polyimide tape (not shown) to form a single-layer electrode body. It should be noted that the negative electrode sheet and the positive electrode sheet are stacked in such a way that the periphery of the stacked positive electrode sheet is surrounded by the inner side of the periphery of the negative electrode sheet.
[0369] Next, the single-layer electrode body is housed in an aluminum laminated outer package 16, and an electrolyte is injected into it. As the electrolyte, a solution obtained by dissolving lithium hexafluorophosphate (LiPF6) as the electrolyte in a solvent at a concentration of 1 mol / L, and further mixing it with vinylene carbonate (VC) at a concentration of 1% by mass, is used. As the solvent, a solution obtained by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3:7 is used.
[0370] Then, with the positive and negative electrode leads extended, the aluminum laminate outer packaging 16 is heat-fused together. Through the above process, the sealed lithium-ion secondary batteries 10 of Examples 1-8 and Comparative Examples 1-8 are obtained.
[0371] <Charge and discharge test of the battery for evaluation (1)>
[0372] The following charge-discharge tests were conducted on the lithium-ion secondary batteries 10 of Examples 1-8 and Comparative Examples 1-8.
[0373] First, a preliminary test was conducted to detect battery anomalies. Specifically, the battery was placed in a constant temperature chamber at 25°C and charged at a constant current of 4mA until the battery voltage reached 4.2V. After a 10-minute rest period, it was discharged at the same constant current until the battery voltage reached 3.0V. This charging, rest, and discharging cycle was defined as one charge-discharge cycle, and three such cycles were repeated under the same conditions as a preliminary test.
[0374] This preliminary test confirmed that all batteries from Examples 1-8 and Comparative Examples 1-8 were free of abnormalities. Based on this, the following formal tests were conducted. It should be noted that the preliminary test was not included in the number of cycles of the formal tests.
[0375] In the formal test, the battery was placed in a constant temperature chamber at 25°C and subjected to constant current / constant voltage charging with a charging current of 30mA, a charging voltage of 4.2V, and a charging time of 3 hours. After a 10-minute rest, the battery was discharged at the same current (30mA) until the battery voltage reached 3.0V. This charging, rest, and discharging cycle was defined as one charge-discharge cycle. The same charge-discharge cycle was repeated three times, and the discharge capacity of the third cycle was defined as the "initial discharge capacity".
[0376] Next, the battery was placed in a constant temperature bath set to -10°C for 5 hours, and then the charge-discharge cycle was repeated 100 times under the same conditions as the charge-discharge cycle used to determine the initial discharge capacity. After that, the battery was placed in a constant temperature bath at 25°C for 5 hours, and then the charge-discharge cycle was repeated 3 times under the same conditions as the charge-discharge cycle used to determine the initial discharge capacity. The discharge capacity of the third cycle was set as "the discharge capacity after repeated charge-discharge cycles at -10°C".
[0377] As an indicator of capacity degradation after repeated charge-discharge cycles at -10°C, the following formula (Equation 1) is used to calculate the retention rate (%) of the discharge capacity after repeated charge-discharge cycles at -10°C relative to the initial discharge capacity mentioned above. The results are shown in Table 1.
[0378]
[0379]
[0380] As shown in Table 1, for the negative electrodes of the lithium-ion secondary batteries of Examples 1-8, the volatile content was below 3.71% and the true density was above 1.22 g / cm³. 3 And below 1.73 g / cm 3 The range of heat-treated raw carbon powder and the artificial graphite material obtained by the manufacturing method of the present invention.
[0381] For the lithium-ion secondary batteries of Examples 1 to 8, the "discharge capacity retention rate (%) after repeated charge-discharge cycles at -10°C" is 67% or higher. This confirms that the discharge capacity of the lithium-ion secondary battery using a negative electrode comprising the artificial graphite material obtained by the manufacturing method of the present invention is not easily degraded even after repeated charge-discharge cycles at -10°C.
[0382] Furthermore, as shown in Table 1, for the lithium-ion secondary batteries of Examples 1 to 8, the "discharge capacity retention rate after repeated charge and discharge at -10°C" is 67.5% or higher. This confirms that the lithium-ion secondary batteries using a negative electrode comprising the artificial graphite material used for the negative electrode of the lithium-ion secondary batteries of Examples 1 to 8 do not easily suffer from capacity degradation even after repeated rapid charging.
[0383] On the other hand, for the negative electrode of the lithium-ion secondary battery of Comparative Example 1, an artificial graphite material obtained by using heat-treated raw material carbon powder with a volatile content of less than 3.71% was utilized.
[0384] For the negative electrodes of the lithium-ion secondary batteries in Comparative Examples 4, 5, and 6, a true density exceeding 1.22 g / cm³ was used. 3 And below 1.73 g / cm3 Artificial graphite materials are obtained from heat-treated raw carbon powder outside the scope of the standard.
[0385] For the negative electrodes of the lithium-ion secondary batteries in Comparative Examples 2, 7, and 8, the volatile content was below 3.71% and the true density was above 1.22 g / cm³. 3 And below 1.73 g / cm 3 Artificial graphite materials are obtained from heat-treated raw carbon powder outside the scope of the standard.
[0386] For the negative electrode of the lithium-ion secondary battery in Comparative Example 3, an artificial graphite material was obtained using raw carbon powder that had not undergone heat treatment and whose volatile content was outside the range of 3.71%.
[0387] It was confirmed that the discharge capacity retention rate (%) of the lithium-ion secondary batteries in Comparative Examples 1 to 8 after repeated charge and discharge at -10°C was less than 46%, and the discharge capacity was more prone to deterioration compared with Examples 1 to 8.
[0388] (Example 9)
[0389] Process A
[0390] The same procedure as in Example 1 was followed to obtain the raw material carbon composition.
[0391] Process B
[0392] In Example 1, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used. Otherwise, the heat treatment raw material carbon composition of Example 9 was obtained by the same method as in Example 1.
[0393] Process C
[0394] The heat-treated raw material carbon composition obtained in Example 9 was pulverized using a hammer mill with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 9.
[0395] Process D
[0396] The raw carbon powder from Example 9 was placed in a graphite crucible, which was then buried in the heating material, insulation material, and filler coke within an Archeson electric furnace, and graphitized at 2950°C. As a graphitization process, the heating time from room temperature to 2950°C was set to 130 hours, the holding time at 2950°C was set to 8 hours, and the powder was removed after cooling for 25 days to obtain graphite powder.
[0397] Process E
[0398] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 14.5 to 15.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Example 9.
[0399] (Example 10)
[0400] Process A
[0401] The same procedure as in Example 2 was followed to obtain the raw material carbon composition.
[0402] Process B
[0403] In Example 2, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 98:2 was used. Otherwise, the heat treatment raw material carbon composition of Example 10 was obtained by the same method as in Example 2.
[0404] Process C
[0405] The heat-treated raw material carbon composition of Example 10 was pulverized using a hammer mill to obtain the raw material carbon powder of Example 10, with an average particle size of 14.5 to 15.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0406] Process D
[0407] The raw carbon powder of Example 10 was graphitized using the same method as in Example 1 to obtain graphite powder.
[0408] Process E
[0409] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 11.5 to 12.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Example 10.
[0410] (Example 11)
[0411] Process A
[0412] The same procedure as in Example 3 was followed to obtain the raw material carbon composition.
[0413] Process B
[0414] In Example 3, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 90:10 was used. Otherwise, the heat treatment raw material carbon composition of Example 11 was obtained by the same method as in Example 3.
[0415] Process C
[0416] The heat-treated raw material carbon composition obtained in Example 11 was pulverized using a hammer mill with an average particle size ranging from 12.5 to 13.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 11.
[0417] Process D
[0418] The raw carbon powder from Example 11 was placed in a graphite crucible and graphitized in a high-frequency induction furnace under a nitrogen atmosphere at 2850°C. As a graphitization process, the heating time from room temperature to 2850°C was set to 23 hours, the holding time at 2850°C was set to 3 hours, and the powder was removed after cooling for 6 days to obtain graphite powder.
[0419] Process E
[0420] The obtained graphite powder was pulverized using an air jet mill so that the average particle size, as determined by a laser diffraction particle size distribution measuring device, was in the range of 8.5 to 9.5 μm, to obtain the artificial graphite material for lithium-ion secondary battery anodes of Example 11.
[0421] (Example 12)
[0422] Process A
[0423] The same procedure as in Example 4 was followed to obtain the raw material carbon composition.
[0424] Process B
[0425] In Example 4, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used. Otherwise, the heat treatment raw material carbon composition of Example 12 was obtained by the same method as in Example 4.
[0426] Process C
[0427] The heat-treated raw material carbon composition obtained in Example 12 was pulverized using a hammer mill to obtain the raw material carbon powder of Example 12, with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0428] Process D
[0429] The raw carbon powder from Example 12 was placed in a graphite crucible and graphitized in a high-frequency induction furnace at 2850°C under a nitrogen atmosphere. The graphitization process involved setting the heating time from room temperature to 2850°C to 23 hours, the holding time at 2850°C to 3 hours, and then cooling for 6 days before removing the powder to obtain graphite powder.
[0430] Process E
[0431] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 10.5 to 11.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Example 12.
[0432] (Example 13)
[0433] Process A
[0434] The same procedure as in Example 5 was followed to obtain the raw material carbon composition.
[0435] Process B
[0436] In Example 5, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used. Otherwise, the heat treatment raw material carbon composition of Example 13 was obtained by the same method as in Example 3.
[0437] Process C
[0438] The obtained heat-treated raw material carbon composition was pulverized using a hammer mill with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw material carbon powder of Example 13.
[0439] Process D and Process E
[0440] The raw carbon powder of Example 13 was used instead of the raw carbon powder of Example 12, and was pulverized by an air jet mill with an average particle size in the range of 8.5 to 9.5 μm. Otherwise, the artificial graphite material for lithium-ion secondary battery negative electrode of Example 13 was obtained by the same method as in Example 12.
[0441] (Comparative Example 9)
[0442] Process A
[0443] The same procedure as in Comparative Example 1 was followed to obtain the raw material carbon composition.
[0444] Low-Temperature Heat Treatment Process
[0445] In Comparative Example 1, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used instead of nitrogen. Otherwise, the heat treatment raw material carbon composition of Comparative Example 9 was obtained by the same method as in Comparative Example 1.
[0446] Process C
[0447] The heat-treated raw carbon composition of Comparative Example 9 was pulverized using a hammer mill to obtain the raw carbon powder of Comparative Example 9, with an average particle size ranging from 17.5 to 18.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0448] Process D and Process E
[0449] The raw carbon powder of Comparative Example 9 was used instead of the raw carbon powder of Example 12. The powder was pulverized by an air jet mill with an average particle size in the range of 14.5 to 15.5 μm. Otherwise, the artificial graphite material for the negative electrode of lithium-ion secondary battery of Comparative Example 9 was obtained by the same method as in Example 12.
[0450] (Comparative Example 10)
[0451] Process A
[0452] The same procedure as in Comparative Example 1 was followed to obtain the raw material carbon composition.
[0453] High-Temperature Heat Treatment Process
[0454] In Comparative Example 2, instead of nitrogen, heating was performed at 750°C under a mixed gas flow of nitrogen and oxygen in a volume ratio of 99:1 to obtain the heat treatment raw material carbon composition of Comparative Example 10.
[0455] Process C
[0456] The heat-treated raw carbon composition of Comparative Example 10 was pulverized using a hammer mill with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device to obtain the raw carbon powder of Comparative Example 10.
[0457] Process D and Process E
[0458] Except that the raw material carbon powder of Comparative Example 10 was used instead of the raw material carbon powder of Example 12, the artificial graphite material for the negative electrode of lithium-ion secondary battery of Comparative Example 10 was obtained by the same method as that of Example 12.
[0459] (Comparative Example 11)
[0460] Process A
[0461] The same procedure as in Example 1 was followed to obtain the raw material carbon composition.
[0462] Heat Treatment Process
[0463] In the manufacturing method of the artificial graphite material for the negative electrode of a lithium-ion secondary battery in Comparative Example 11, no heat treatment of the raw material carbon composition was performed.
[0464] Process C
[0465] The raw carbon composition of Example 1 was pulverized using a hammer mill to obtain raw carbon powder, with an average particle size ranging from 17.5 to 18.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0466] Process D
[0467] The raw carbon powder of Comparative Example 11 obtained by such operation was graphitized using the same method as in Example 9 to obtain graphite powder.
[0468] Process E
[0469] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 12.5 to 13.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for the negative electrode of a lithium-ion secondary battery of Comparative Example 11.
[0470] (Comparative Example 12)
[0471] Process A
[0472] The same procedure as in Comparative Example 4 was followed to obtain the raw material carbon composition.
[0473] Process B
[0474] In Comparative Example 4, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used. Otherwise, the heat treatment raw material carbon composition of Comparative Example 12 was obtained by the same method as in Comparative Example 4.
[0475] Process C
[0476] The heat-treated raw carbon composition of Comparative Example 12 was pulverized using a hammer mill with an average particle size ranging from 15.5 to 16.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw carbon powder of Comparative Example 12.
[0477] Process D and Process E
[0478] The raw carbon powder of Comparative Example 12 was used instead of the raw carbon powder of Example 12. The powder was pulverized by an air jet mill with an average particle size in the range of 13.5 to 14.5 μm. Otherwise, the artificial graphite material for lithium-ion secondary battery negative electrode of Comparative Example 12 was obtained by the same method as in Example 12.
[0479] (Comparative Example 13)
[0480] Process A
[0481] The same procedure as in Comparative Example 5 was followed to obtain the raw material carbon composition.
[0482] Process B
[0483] In Comparative Example 5, a mixed gas with a nitrogen to oxygen volume ratio of 98:2 was used instead of nitrogen. Otherwise, the heat treatment raw material carbon composition of Comparative Example 13 was obtained by the same method as in Comparative Example 5.
[0484] Process C
[0485] The heat-treated raw carbon composition of Comparative Example 13 was pulverized using a hammer mill with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device to obtain the raw carbon powder of Comparative Example 13.
[0486] Process D
[0487] The raw carbon powder of Comparative Example 13 was placed in a crucible made of graphite and graphitized in a high-frequency induction furnace under a nitrogen flow at 2850°C. As a graphitization process, the heating time from room temperature to 2850°C was set to 23 hours, the holding time at 2850°C was set to 3 hours, and the powder was removed after cooling for 6 days to obtain graphite powder.
[0488] Process E
[0489] The obtained graphite powder was pulverized using an air jet mill so that the average particle size, as determined by a laser diffraction particle size distribution measuring device, was in the range of 7.5 to 8.5 μm, to obtain the artificial graphite material for the negative electrode of a lithium-ion secondary battery of Comparative Example 13.
[0490] (Comparative Example 14)
[0491] Process A
[0492] The same procedure as in Comparative Example 6 was followed to obtain the raw material carbon composition.
[0493] Process B
[0494] In Comparative Example 6, a mixed gas with a nitrogen to oxygen volume ratio of 90:10 was used instead of nitrogen. Otherwise, the heat treatment raw material carbon composition of Comparative Example 14 was obtained by the same method as in Comparative Example 6.
[0495] Process C
[0496] The heat-treated raw carbon composition of Comparative Example 14 was pulverized using a hammer mill with an average particle size ranging from 18.5 to 19.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the raw carbon powder of Comparative Example 14.
[0497] Process D
[0498] The raw carbon powder of Comparative Example 14 was graphitized using the same method as in Example 9 to obtain graphite powder.
[0499] Process E
[0500] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 7.5 to 8.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 14.
[0501] (Comparative Example 15)
[0502] Process A
[0503] The same procedure as in Comparative Example 7 was followed to obtain the raw material carbon composition.
[0504] Process B
[0505] In Comparative Example 7, a mixed gas with a nitrogen to oxygen volume ratio of 94:6 was used instead of nitrogen. Otherwise, the heat treatment raw material carbon composition of Comparative Example 15 was obtained by the same method as in Comparative Example 7.
[0506] Process C
[0507] The heat-treated raw carbon composition of Comparative Example 15 was pulverized using a hammer mill to obtain the raw carbon powder of Comparative Example 15, with an average particle size ranging from 20.5 to 21.5 μm as determined by a laser diffraction particle size distribution measuring device.
[0508] Process D
[0509] The raw carbon powder of Comparative Example 15 was graphitized using the same method as in Example 9 to obtain graphite powder.
[0510] Process E
[0511] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 11.5 to 12.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery negative electrode of Comparative Example 15.
[0512] (Comparative Example 16)
[0513] Process A
[0514] The same procedure as in Comparative Example 8 was followed to obtain the raw material carbon composition.
[0515] Process B
[0516] In Comparative Example 8, instead of nitrogen, a mixed gas with a nitrogen to oxygen volume ratio of 83:17 was used. Otherwise, the heat treatment raw material carbon composition of Comparative Example 16 was obtained by the same method as in Comparative Example 8.
[0517] Process C
[0518] The heat-treated raw carbon composition of Comparative Example 16 was pulverized using a hammer mill to obtain the raw carbon powder of Comparative Example 16, with the average particle size measured by a laser diffraction particle size distribution measuring device being in the range of 17.5 to 18.5 μm.
[0519] Process D
[0520] The raw carbon powder of Comparative Example 16 was placed in a crucible made of graphite and graphitized in a high-frequency induction furnace under a nitrogen flow at 2850°C. As a graphitization process, the heating time from room temperature to 2850°C was set to 23 hours, the holding time at 2850°C was set to 3 hours, and the powder was removed after cooling for 6 days to obtain graphite powder.
[0521] Process E
[0522] The obtained graphite powder was pulverized using an air jet mill with an average particle size ranging from 10.5 to 11.5 μm as determined by a laser diffraction particle size distribution measuring device, to obtain the artificial graphite material for lithium-ion secondary battery anode of Comparative Example 16.
[0523] (Example 14)
[0524] The artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 were mixed in a mass ratio of 50:50 to form a mixture, and the artificial graphite material for lithium-ion secondary battery negative electrode of Example 14 was formed from the mixture.
[0525] (Example 15)
[0526] The artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 were mixed in a mass ratio of 30:70 to form a mixture, and the artificial graphite material for lithium-ion secondary battery negative electrode of Example 15 was formed from the mixture.
[0527] (Example 16)
[0528] The artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 were mixed in a mass ratio of 20:80 to form a mixture, and the artificial graphite material for lithium-ion secondary battery negative electrode of Example 16 was formed from the mixture.
[0529] For the artificial graphite materials used as negative electrodes in lithium-ion secondary batteries in Examples 9-13 and Comparative Examples 9-16, the crystallite size L (112), nitrogen adsorption specific surface area S (BET), ESR signal intensity I (4.8K) at 4.8K, and ratio I (4.8K) / S (BET) were determined using the same method as in Example 1. The results are shown in Table 2.
[0530] <Evaluation of Battery Manufacturing (2)>
[0531] Any of the artificial graphite materials obtained in Examples 9-16 and Comparative Examples 9-16 were used instead of any of the artificial graphite materials obtained in Examples 1-8 and Comparative Examples 1-8 as the positive electrode material. A composite oxide of nickel, cobalt, manganese, and lithium, NCM523 (manufactured by Beijing Easpring Material Technology Co., Ltd.), with an average particle size of 12 μm, was used instead of lithium cobalt oxide (LiCoO2) with an average particle size of 10 μm. The coating amount of the positive electrode agent per unit area in the positive electrode sheet was approximately 17.2 mg / cm³ based on the mass of NCM523. 2 The method was adjusted so that, instead of the solvent obtained by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, the solvent obtained by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3 was used. Otherwise, the same procedure as described in “Preparation of Evaluation Battery (1)” was followed to obtain the sealed lithium-ion secondary batteries 10 of Examples 9 to 16 and Comparative Examples 9 to 16.
[0532] <Battery charge / discharge test for evaluation (2)>
[0533] The lithium-ion secondary batteries 10 of Examples 9-16 and Comparative Examples 9-16 were evaluated in the same manner as in the "Charge-Discharge Test (1) of the Evaluation Battery" described above. The results are shown in Table 2.
[0534]
[0535] As shown in Table 2, for the negative electrode of the lithium-ion secondary batteries of Examples 9-16, the following artificial graphite material was used as the negative electrode. This artificial graphite material is characterized by a crystallite size L(112) of 4-30 nm, calculated from the (112) diffraction line determined by wide-angle X-ray diffraction, and a nitrogen adsorption specific surface area S(BET) of 2.5-6.2 m². 2 / g, in the electron spin resonance method using X-rays, exhibits an absorption spectrum originating from carbon radicals appearing near g = 2.0. The ratio of spin density I(4.8K)(spins / g) to S(BET), calculated from the signal intensity at 4.8K, is I(4.8K) / S(BET) = 5.2 × 10⁻⁶. 17 ~6.8×10 17 spins / m 2 Furthermore, it utilized a volatile content range of less than 3.71% and a true density exceeding 1.22 g / cm³. 3 And below 1.73 g / cm 3 The range of heat-treated raw carbon powder and the artificial graphite material obtained by the manufacturing method of the present invention.
[0536] For the lithium-ion secondary batteries of Examples 9 to 16, the "discharge capacity retention rate (%) after repeated charge-discharge cycles at -10°C" is 75% or more. This confirms that the lithium-ion secondary battery using the artificial graphite material of the present invention and the negative electrode containing the artificial graphite material obtained by the manufacturing method of the present invention does not easily degrade in discharge capacity even after repeated charge-discharge cycles at -10°C.
[0537] Furthermore, as shown in Table 2, for the lithium-ion secondary batteries of Examples 9 to 16, the "discharge capacity retention rate after repeated charge and discharge at -10°C" is 75.5% or higher. This confirms that the discharge capacity of lithium-ion secondary batteries using a negative electrode comprising the artificial graphite material used for the negative electrode of lithium-ion secondary batteries of Examples 9 to 16 is not easily degraded even with repeated rapid charging.
[0538] On the other hand, the S(BET) of the negative electrode of the lithium-ion secondary batteries of Comparative Examples 10, 11, 15, and 16 is within the scope of the present invention, while I(4.8K) / S(BET) is outside the scope of the present invention.
[0539] The negative electrode of the lithium-ion secondary batteries of Comparative Examples 12 and 13 has an I(4.8K) / S(BET) ratio within the scope of the present invention, while S(BET) is outside the scope of the present invention.
[0540] The S(BET) and I(4.8K) / S(BET) of the negative electrode of the lithium-ion secondary batteries in Comparative Examples 9 and 14 are outside the scope of this invention.
[0541] It was confirmed that the discharge capacity retention rate (%) of the lithium-ion secondary batteries of Comparative Examples 9 to 16 after repeated charge and discharge at -10°C was less than 64%, and the discharge capacity was more prone to deterioration compared with Examples 9 to 16.
[0542] Furthermore, for the negative electrode of the lithium-ion secondary battery in Comparative Example 9, an artificial graphite material obtained by using heat-treated raw material carbon powder with a volatile content of less than 3.71% was utilized.
[0543] For the negative electrodes of the lithium-ion secondary batteries in Comparative Examples 12, 13, and 14, a true density exceeding 1.22 g / cm³ was used. 3 And below 1.73 g / cm 3 Artificial graphite materials are obtained from heat-treated raw carbon powder outside the scope of the standard.
[0544] For the negative electrodes of the lithium-ion secondary batteries in Comparative Examples 10, 15, and 16, electrodes with volatile content below 3.71% and true density exceeding 1.22 g / cm³ were used. 3 And below 1.73 g / cm 3 Artificial graphite materials are obtained from heat-treated raw carbon powder outside the scope of the standard.
[0545] For the negative electrode of the lithium-ion secondary battery in Comparative Example 11, an artificial graphite material was used, which was obtained by using raw carbon powder that had not undergone heat treatment and whose volatile content was outside the range of 3.71%.
[0546] Industrial availability
[0547] A lithium-ion secondary battery having a negative electrode comprising an artificial graphite material obtained by the manufacturing method of the artificial graphite material for lithium-ion secondary battery negative electrode of the present invention becomes a battery whose discharge capacity is not easily degraded even after repeated charge and discharge at a low temperature of -10°C. Therefore, a lithium-ion secondary battery having a negative electrode comprising an artificial graphite material obtained by the manufacturing method of the artificial graphite material for lithium-ion secondary battery negative electrode of the present invention is preferably used for industrial applications such as hybrid electric vehicles, plug-in hybrid electric vehicles, electric vehicles, etc., and for power storage in public infrastructure systems.
[0548] Explanation of symbols
[0549] 10…Lithium-ion secondary batteries
[0550] 11… Negative electrode
[0551] 12… Negative current collector
[0552] 13… Positive electrode
[0553] 14…Positive current collector
[0554] 15…Septum
[0555] 16… Aluminum laminated outer packaging
Claims
1. A method for manufacturing an artificial graphite material for the negative electrode of a lithium-ion secondary battery, comprising at least the following steps: The process of producing a raw material carbon composition by coking a raw material oil composition through a delayed coking process at a pressure of 0.1–0.8 MPa and a temperature of 400–600 °C. The process of heat-treating the raw material carbon composition at a temperature of 500°C or higher and 700°C or lower to obtain a heat-treated raw material carbon composition; The process of pulverizing the heat-treated raw material carbon composition to obtain raw material carbon powder with an average particle size of 5 to 40 μm; The process of graphitizing the raw carbon powder to obtain graphite powder; and The process of pulverizing the graphite powder. The volatile content of the raw carbon powder is greater than 0.1% and less than 3.71%, and the true density of the raw carbon powder is greater than 1.22 g / cm³. 3 And below 1.73 g / cm 3 , The feedstock oil composition has a n-alkanes content of 5-20% by mass and an aromatic index fa of 0.3-0.65 determined by the Knight method.
2. The method for manufacturing artificial graphite material for the negative electrode of a lithium-ion secondary battery according to claim 1, wherein, The graphitization process involves calcining the raw carbon powder to remove volatile components to obtain calcined coke, followed by a carbonization treatment and then a graphitization treatment. The calcination is a heat treatment performed in an inert gas atmosphere, with a maximum temperature of 500–1500°C and a holding time of the maximum temperature of 0–10 hours. The carbonization process is a heat treatment performed in an inert gas atmosphere, with a maximum temperature of 500–1500°C and a holding time of 0–10 hours at the maximum temperature. The graphitization process is a heat treatment performed in an inert gas atmosphere, with a maximum temperature of 2500–3200°C and a holding time of 0–100 hours at the maximum temperature.
3. A negative electrode for a lithium-ion secondary battery, comprising an artificial graphite material obtained by the manufacturing method of claim 1 or 2.
4. A lithium-ion secondary battery having the negative electrode as described in claim 3.
5. The artificial graphite material for the negative electrode of a lithium-ion secondary battery obtained by the manufacturing method according to claim 1 or 2, characterized in that, The nitrogen adsorption specific surface area S (BET) is 2.5–6.2 m². 2 / g, Using the X-band electron spin resonance method, an absorption spectrum originating from carbon radicals appearing near g=2.0 was obtained. The ratio of spin density I(4.8K) to S(BET), calculated from the signal intensity at 4.8K, is I(4.8K) / S(BET) = 5.2 × 10⁻⁶. 17 ~6.8×10 17 spins / m 2 The unit of the spin density I (4.8K) is spins / g.
Citation Information
Patent Citations
JP1979015684A
Aqueous ink for inkjet printing
JP2020105303A
Negative electrode carbon material for lithium secondary battery and method for manufacturing same
CN102511096A
Low-temperature burned carbon for material of electrode
JP2007019257A